Electrophotographic image forming system

By using electronic absorption characteristics thermoplastic resin and keratin metal salt in the electro-optical image formation system, and optimizing the edge and contact angles of the cleaning knife, the colloidal coating deposition problem is solved, and the image quality is maintained for a long time and the stable operation of the system is achieved.

JP2025061608AActive Publication Date: 2025-04-10KONICA MINOLTA INC
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2025009370
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-10
Estimated Expiration
2041-01-07

AI Technical Summary

Technical Problem

During long-term operation, existing electro-optical image forming systems are prone to colloidal coating deposition of colloidal coating on the surface of the photosensitive device (i.e. colloidal coating deposition), resulting in image defects.

Method used

The thermoplastic resin with electron absorption characteristics is used as the surface material of the photosensitive device, and the fatty acid metal salt is added as the external additive to the colloidal coating. At the same time, the edge angle of the cleaning knife is 90 to 130 degrees, and the effective contact angle of the cleaning knife is between 7 to 20 degrees.

Benefits of technology

Effectively prevent the deposition of colloidal coatings on the photosensitive surface, maintain image quality, and ensure the stability and image clarity of the system during long-term operation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025061608000001_ABST
    Figure 2025061608000001_ABST
Patent Text Reader

Abstract

To provide an image forming system that can obtain a satisfactory image for a long period without causing toner filming on a surface of a photoreceptor.SOLUTION: An electrophotographic image forming system includes the steps of: forming an electrostatic latent image at least on a photoreceptor; performing development by using a toner for electrostatic charge image development; and bringing a leading end ridge part of a cleaning blade into pressure contact with a surface of the photoreceptor to remove the toner for electrostatic charge image development. A surface layer of the photoreceptor contains a thermoplastic resin having at least electron acceptability. Toner particles constituting the toner for electrostatic charge image development each contain at least a fatty acid metal salt in its surface as an external additive. A leading end ridge part of a cleaning blade having an edge angle within a range of 90-130° is brought into pressure contact with a surface of the photoreceptor, and the effective contact angle of the cleaning blade is within a range of 7-20°.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to electrophotographic imaging systems. More particularly, the present invention relates to an image forming system capable of obtaining good images for a long period of time without causing toner filming on the surface of a photoconductor. [Background technology]

[0002] 2. Description of the Related Art Nowadays, in electrophotographic image forming apparatuses using toner for developing electrostatic images (hereinafter also simply referred to as "toner"), the occurrence of toner filming due to insufficient lubricity on the surface of a photoreceptor has become a problem. Toner filming is a phenomenon in which external additives and toner components adhere to the surface of a photoreceptor as nuclei, and then the external additives and toner particles themselves adhere to the nuclei, growing into large raindrop-like lumps. When toner filming occurs, the light exposure that forms a latent image is blocked in the affected areas, causing image defects such as those areas appearing as blank areas in the image. Conventionally, a method for preventing toner filming has been known in which a lubricant (fatty acid metal salt) is added to the toner base particles and supplied to the surface of the photoreceptor in order to lubricate the surface of the photoreceptor and improve cleaning performance. However, in the above-mentioned method, it is difficult to ensure a sufficient amount of lubricant (coverage rate) from the viewpoints of various functions as a developer and fixing performance, and the effect of improving toner filming is insufficient.

[0003] Patent Document 1 proposes a method of forming the edge portion of a cleaning blade into an obtuse angle shape. Here, FIG. 1 shows a cleaning blade C L When the edge E of the cleaning blade C is not obtuse, the toner particles T may be L 1 is a conceptual diagram showing the direction of the force acting from and the state of fatty acid metal salt M. Figure 2 shows the cleaning blade C L When the edge E of the cleaning blade C has an obtuse angle, the toner particles T areL 1 is a conceptual diagram showing the direction of the force acting from and the state of fatty acid metal salt M. Comparing Figure 1 and Figure 2, Figure 2 shows that cleaning blade C L Since the edge E of the cleaning blade 10 has an obtuse angle, the wedge angle θ3 in the wedge-shaped portion upstream of the cleaning blade nip is small, and the force F that presses the toner particles and hard particles against the photoconductor surface in the vertical direction is small. N Therefore, the polishing power is improved. However, because the above-mentioned effect also makes it easier to remove the fatty acid metal salt from the surface of the photoreceptor, the effect of improving toner filming is insufficient from the viewpoint of achieving both lubricity and abrasive power. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 5-19671 Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention has been made in consideration of the above problems and circumstances, and the problem to be solved by this invention is to provide an image forming system that can obtain good images over a long period of time without causing toner filming on the photoreceptor surface. [Means for solving the problem]

[0006] In the course of investigating the causes of the above problems in order to solve the above problems, the present inventors discovered that the above problems can be solved by an electrophotographic image forming system characterized in that the surface layer of a photoreceptor contains a thermoplastic resin having electron accepting properties, the toner particles contain a fatty acid metal salt, and the system uses a cleaning blade having an edge angle in the range of 90 to 130° and an effective contact angle in the range of 7 to 20°, thereby arriving at the present invention. That is, the above-mentioned problems of the present invention are solved by the following means.

[0007] 1. forming an electrostatic latent image on at least a photoconductor; developing the image with a toner for developing an electrostatic image; and removing the toner for developing the electrostatic image by pressing a ridge portion of a cleaning blade against the surface of the photoconductor, the photoreceptor has a photosensitive layer and a surface layer on a conductive support, the surface layer containing at least a thermoplastic resin having a LUMO level lower than 1.4 eV; The toner particles constituting the electrostatic image developing toner contain at least a fatty acid metal salt on the surface as an external additive, an edge portion of a cleaning blade having an edge angle in the range of 90° to 130° is pressed against the surface of the photoreceptor, and an effective contact angle of the cleaning blade is in the range of 7° to 20°.

[0008] 2. The electrophotographic imaging system of claim 1, wherein said edge angle is an obtuse angle of 95° or greater.

[0009] 3. The electrophotographic imaging system according to claim 1 or 2, wherein the thermoplastic resin having a LUMO level lower than 1.4 eV is a polyimide resin containing an electron-withdrawing group.

[0010] 4. An electrophotographic imaging system according to any one of claims 1 to 3, wherein the edge angle is 110° or less.

[0011] 5. The electrophotographic image forming system according to any one of items 1 to 4, wherein the amount of the fatty acid metal salt added is within a range of 0.20 to 0.30% by mass based on the toner base particles.

[0012] 6. The electrophotographic imaging system according to any one of claims 1 to 5, wherein the fatty acid metal salt is zinc stearate. Effect of the Invention

[0013] According to the above-mentioned means of the present invention, it is possible to provide an image forming system capable of obtaining good images for a long period of time without causing toner filming on the surface of the photoreceptor.

[0014] Although the mechanism by which the effects of the present invention are expressed or the mechanism of action has not been clarified, it is speculated as follows. In the present invention, a fatty acid metal salt is contained as an external additive in the toner base particles, and a cleaning blade having a blunt edge is combined with a photoreceptor having a surface layer containing a thermoplastic resin having electron accepting properties, and used as an electrophotographic image forming system.

[0015] FIG. 3 shows the toner particles T in the present invention. L 1 is a conceptual diagram showing the direction of force F acting from and the state of fatty acid metal salt M. In the present invention, the above-mentioned fatty acid metal salt (lubricant) is used in combination with a resin having electron-accepting properties, resulting in high affinity and making it easier for the lubricant to be fixed to the photoreceptor. Although the reason for this is unclear, it is presumed that the affinity is high because fatty acid metal salt M is generally known to have positive charging properties, and the alkyl terminal portion of the fatty acid, which becomes the crystal cleavage plane, has electron-donating properties.

[0016] As a result of the above, the edge angle θ e A cleaning blade C having an obtuse angle shape falling within the above range L In the wedge-shaped portion upstream of the blade nip, the toner particles T press the photoconductor 10 in the vertical direction F N Even under high abrasive conditions, the lubricant is difficult to remove due to the toner and hard particles, and tends to penetrate into the blade nip.

[0017] If the fatty acid metal salt reaches the vicinity of the blade nip without being removed by the wedge-shaped portion, the obtuse shape of the blade edge reduces the wedge angle θ3, so that the fatty acid metal salt is subjected to a shearing action that cleaves and spreads the layered crystals, making it more likely to be fixed on the photoreceptor.

[0018] Due to the above synergistic effect, the lubricity of the photoreceptor surface can be significantly improved, and toner filming can be suppressed. [Brief description of the drawings]

[0019] [Figure 1] A conceptual diagram showing the direction of the force that the cleaning blade exerts on the toner particles and the state of the fatty acid metal salt when the edge of the cleaning blade is not obtuse. [Diagram 2] A conceptual diagram showing the direction of the force that the cleaning blade exerts on the toner particles and the state of the fatty acid metal salt when the edge of the cleaning blade has an obtuse angle. [Diagram 3] A conceptual diagram showing the direction of the force applied to the toner particles by the cleaning blade and the state of the fatty acid metal salt in the present invention. [Figure 4] Schematic diagram of the optical absorption spectrum observed in a mixture of an electron donor (reference material) and a thermoplastic resin. [Diagram 5] A schematic diagram showing the relationship between the cleaning blade and the electrophotographic photoreceptor according to the present invention, as viewed from the side. [Figure 6] FIG. 1 is a cross-sectional view illustrating an example of a configuration of an image forming apparatus according to the present invention. [Figure 7] FIG. 1 is an explanatory cross-sectional view showing an example of a configuration of a main part of an image forming apparatus. [Figure 8] FIG. 1 is a schematic diagram showing an example of the configuration of a charging unit of an image forming apparatus used in the present invention. [Figure 9] Conceptual diagram of toner filming count DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] The electrophotographic image forming system of the present invention is an electrophotographic image forming system having at least a step of forming an electrostatic latent image on a photoreceptor, a step of developing the image using a toner for developing an electrostatic image, and a step of removing the toner for developing an electrostatic image by pressing a ridgeline of a cleaning blade against the surface of the photoreceptor, wherein the photoreceptor has a photosensitive layer and a surface layer on a conductive support, the surface layer contains at least a thermoplastic resin having a LUMO level lower than 1.4 eV, the toner particles constituting the toner for developing an electrostatic image contain at least a fatty acid metal salt on the surface as an external additive, the ridgeline of a cleaning blade having an edge angle in the range of 90 to 130° is pressed against the surface of the photoreceptor, and the effective contact angle of the cleaning blade is in the range of 7 to 20°. This feature is a technical feature common to or corresponding to each of the following embodiments (configurations).

[0021] As an embodiment of the present invention, it is preferable that the edge angle is an obtuse angle of 95° or more from the viewpoint of sufficiently improving the lubricity of the surface.

[0022] In addition, it is preferable that the thermoplastic resin having a LUMO level lower than 1.4 eV is a polyimide resin containing an electron-withdrawing group, from the viewpoint of enhancing the electron-accepting property and improving the affinity with the fatty acid metal salt.

[0023] From the viewpoint of sufficiently improving the lubricity of the surface, it is preferable that the edge angle is 110° or less.

[0024] From the viewpoint of sufficiently improving the lubricity of the surface, it is preferable that the amount of the fatty acid metal salt added is within a range of 0.20 to 0.30% by mass based on the toner base particles.

[0025] From the viewpoint of improving the lubricity of the surface, it is preferable that the fatty acid metal salt is zinc stearate.

[0026] The present invention, its components, and embodiments for carrying out the present invention will be described in detail below. In this application, the symbol "to" is used to mean that the numerical values ​​before and after the symbol "to" are included as the lower limit and upper limit.

[0027] [Overview of the electrophotographic image forming system of the present invention] The electrophotographic image forming system of the present invention is an electrophotographic image forming system having at least a step of forming an electrostatic latent image on a photoreceptor, a step of developing the image using a toner for developing an electrostatic image, and a step of removing the toner for developing an electrostatic image by pressing a ridgeline of a cleaning blade against the surface of the photoreceptor, wherein the photoreceptor has a photosensitive layer and a surface layer on a conductive support, the surface layer contains at least a thermoplastic resin having a LUMO level lower than 1.4 eV, the toner particles constituting the toner for developing an electrostatic image contain at least a fatty acid metal salt on the surface as an external additive, the ridgeline of a cleaning blade having an edge angle in the range of 90 to 130° is pressed against the surface of the photoreceptor, and the effective contact angle of the cleaning blade is in the range of 7 to 20°.

[0028] 1. Electrophotographic Photoreceptor The photoreceptor according to the present invention is an electrophotographic photoreceptor for use in an electrophotographic photosensitive type image forming apparatus, and the photoreceptor has a photosensitive layer and a surface layer on a conductive support, and the surface layer contains at least a thermoplastic resin having a LUMO level lower than 1.4 eV.

[0029] The thermoplastic resin having a LUMO level lower than 1.4 eV is preferably a polyimide resin containing an electron-withdrawing group, from the viewpoint of enhancing the electron-accepting property and improving the affinity with the fatty acid metal salt.

[0030] The thermoplastic resin preferably contains a charge transport material.

[0031] The electrophotographic photoreceptor has a conductive support, a photosensitive layer, and a surface layer. However, the present invention may include configurations other than those described above as long as the object and effect of the present invention are not impaired. For example, other layers such as an intermediate layer may be provided between the conductive support and the photosensitive layer, if necessary.

[0032] Conventional low-molecular-weight electron-accepting compounds tend to be unevenly distributed within the surface layer, and the unevenly distributed electron-accepting compound can trap charges moving within the surface layer. In contrast, in the electrophotographic photoreceptor according to the present invention, since the structure having electron-accepting properties is supported by a thermoplastic resin, the structure is unlikely to be unevenly distributed within the surface layer, and the above-mentioned charge trapping is unlikely to occur.

[0033] (1.1) Conductive support The support used in the present invention may be any structure that is conductive and capable of supporting the photosensitive layer, and is, for example, a cylindrical or columnar structure. The size of the conductive support is appropriately selected depending on the application of the electrophotographic photoreceptor. The material of the conductive support is not particularly limited.

[0034] Examples of the conductive support include metals such as aluminum, copper, chromium, nickel, zinc, stainless steel, etc., formed into a drum or sheet shape; metal foils such as aluminum or copper laminated onto drum-shaped or sheet-shaped plastic films; aluminum, indium oxide, tin oxide, etc., vapor-deposited onto drum-shaped or sheet-shaped plastic films; and drum-shaped or sheet-shaped metals, plastics, or paper on which a conductive layer is formed by applying a conductive material alone, or a composition containing a conductive material and a binder resin, onto drum-shaped or sheet-shaped metals, plastics, or paper.

[0035] (1.2) Photosensitive layer The photosensitive layer may contain a charge generating material capable of generating charges and a charge transport material having charge transport properties, and may be composed of, for example, a charge generating layer containing a charge generating material and a charge transport layer containing a charge transport material. On the other hand, the charge generating material and the charge transporting material may be contained in one layer (charge generating / transporting layer). However, if the charge generating layer and the charge transporting layer are constructed separately, the residual potential is less likely to increase during repeated use of the electrophotographic photoreceptor, and further, the characteristics of each layer are easier to control depending on the purpose of the electrophotographic photoreceptor. Hereinafter, an example will be described in which the charge generating layer and the charge transporting layer are formed separately, but the photosensitive layer of the electrophotographic photoreceptor according to the present invention is not limited to this embodiment.

[0036] (Charge generation layer) The charge generating layer may be any layer capable of generating charges upon irradiation with light, and may be, for example, a layer containing a charge generating substance and a binder resin.

[0037] The charge generating material is not particularly limited, and any known charge generating material can be used. Examples include azo pigments such as Sudan Red and Diane Blue; quinone pigments such as pyrenequinone and anthanthrone; quinocyanine pigments; perylene pigments; indigo pigments such as indigo and thioindigo; phthalocyanine pigments such as titanyl phthalocyanine, and the like. The charge generating layer may contain only one type of these charge generating materials, or may contain two or more types.

[0038] On the other hand, known resins can be used as the binder resin. Examples of such resins include polystyrene resins, polyethylene resins, polypropylene resins, acrylic resins, methacrylic resins, vinyl chloride resins, vinyl acetate resins, polyvinyl butyral resins, epoxy resins, polyurethane resins, phenolic resins, polyester resins, alkyd resins, polycarbonate resins, silicone resins, melamine resins, polyvinylcarbazole resins, and copolymers thereof (e.g., vinyl chloride-vinyl acetate copolymer resins, vinyl chloride-vinyl acetate-maleic anhydride copolymer resins, etc.). The charge generating layer may contain only one type of these binder resins, or may contain two or more types of them.

[0039] The amount of the charge generating material in the charge generating layer is preferably within a range of 1 to 600 parts by mass, and more preferably within a range of 50 to 500 parts by mass, per 100 parts by mass of the binder resin. When the amount of the charge generating material is within this range, a sufficient amount of charge can be generated.

[0040] The thickness of the charge generating layer is appropriately selected depending on the characteristics of the charge generating material, the characteristics and mixing ratio of the binder resin, etc., but is preferably in the range of 0.01 to 5 μm, more preferably in the range of 0.05 to 3 μm. When the thickness of the charge generating layer is within this range, the charge generating ability is likely to be stable, and further, the layer can have a sufficiently high strength.

[0041] (charge transport layer) The charge transport layer may be any layer capable of transporting the charges generated in the charge generation layer, and may be, for example, a layer containing a charge transport material and a binder resin.

[0042] The charge transport material may be any material capable of transporting charge, and may be any known compound.Examples of the charge transport material include carbazole derivatives, oxazole derivatives, oxadiazole derivatives, thiazole derivatives, thiadiazole derivatives, triazole derivatives, imidazole derivatives, imidazolone derivatives, imidazolidine derivatives, bisimidazolidine derivatives, styryl compounds, hydrazone compounds, pyrazoline compounds, oxazolone derivatives, benzimidazole derivatives, quinazoline derivatives, benzofuran derivatives, acridine derivatives, phenazine derivatives, aminostilbene derivatives, triarylamine derivatives, phenylenediamine derivatives, stilbene derivatives, benzidine derivatives, poly-N-vinylcarbazole, poly-1-vinylpyrene, and poly-9-vinylanthracene. The charge transport layer may contain only one of these, or may contain two or more of them.

[0043] On the other hand, known resins can be used as the binder resin. Examples of such resins include polycarbonate resins, polyacrylate resins, polyester resins, polystyrene resins, styrene-acrylonitrile copolymer resins, polymethacrylate resins, styrene-methacrylate copolymer resins, etc. Among these, polycarbonate resins are preferred, and polycarbonate resins containing structures such as bisphenol A (BPA), bisphenol Z (BPZ), dimethyl BPA, and BPA-dimethyl BPA copolymers are particularly preferred from the viewpoints of crack resistance, abrasion resistance, and electrostatic properties. The charge transport layer may contain only one of these, or may contain two or more of them.

[0044] The charge transport layer may contain various additives such as an antioxidant and silicone oil, as long as the object and effect of the present invention are not impaired. Specific examples of the antioxidant include the compounds described in JP-A-2000-305291.

[0045] The amount of the charge transport material in the charge transport layer is preferably within a range of 10 to 500 parts by weight, and more preferably within a range of 20 to 100 parts by weight, per 100 parts by weight of the binder resin. When the amount of the charge transport material is within this range, the charge transporting property of the charge transport layer is good.

[0046] The thickness of the charge transport layer is appropriately selected depending on the characteristics of the charge transport material and binder resin, and the mixing ratio thereof, but is preferably within the range of 5 to 40 μm, and more preferably within the range of 10 to 30 μm. When the thickness of the charge transport layer is within this range, the charge transport ability is likely to be stable, and further, the layer can have a sufficiently high strength.

[0047] (1.3) Surface layer The surface layer functions as a layer for protecting the above-mentioned photosensitive layer from external electrical and mechanical forces. The surface layer may be any layer containing a thermoplastic resin having a LUMO level lower than 1.4 eV, and it is preferable that the thermoplastic resin is a polyimide resin containing an electron-withdrawing group, from the viewpoints of enhancing electron-accepting ability and improving affinity with fatty acid metal salts. In addition, other components may be included as necessary.

[0048] The thermoplastic resin functions as a material for binding the charge transport material in the surface layer, that is, as a binder resin.

[0049] (1.3.1) Electron-accepting In the present invention, the electron accepting property of a thermoplastic resin is determined by indirectly estimating the LUMO level of the thermoplastic resin from a charge transfer absorption band in an optical absorption spectrum observed in a mixed system in which the thermoplastic resin is combined with an electron donor (reference substance) whose highest occupied molecular orbital (HOMO) level is known, as described below.

[0050] (Method for confirming the presence or absence of electron accepting ability) In the present invention, a fatty acid metal salt (lubricant) is used in combination with a resin having electron accepting properties, so that the affinity is increased and the lubricant is easily fixed to the photoreceptor. Therefore, a method for confirming whether a resin has electron accepting properties will be described below.

[0051] It is difficult to directly identify the lowest unoccupied molecular orbital (LUMO) level of a thermoplastic resin itself, but it can be indirectly estimated from the charge-transfer absorption band when combined with an electron donor (reference substance) whose highest occupied molecular orbital (HOMO) level is known. The HOMO level of the reference substance can be measured relatively easily using a commercially available photoelectron spectrometer (eg, AC-3 manufactured by Riken Keiki Co., Ltd.). FIG. 4 is a conceptual diagram showing the observation of an optical absorption spectrum in a mixed system of an electron donor (reference substance) and a thermoplastic resin.

[0052] In the present invention, tetramethyl-p-phenylenediamine (reference substance A, HOMO level 5.0 eV) and 4-propylbiphenyl-bis(4-methylphenyl)amine (reference substance B, HOMO level 5.6 eV, CTM-3), which are represented by the chemical formulas below, are used as electron donors (reference substances). When judging whether a thermoplastic resin has electron accepting properties, those which can be judged to have electron accepting properties in a mixed system of a thermoplastic resin and reference substance A and which can be judged to have electron accepting properties in a mixed system of a thermoplastic resin and reference substance B are preferred because they have higher electron accepting properties.

[0053] [ka]

[0054] [ka]

[0055] In the following description, an example will be described in which the presence or absence of electron accepting property is confirmed using a compound reference substance A having a structure represented by the following chemical formula as an electron donor (reference substance).

[0056] First, the target thermoplastic resin is extracted from the surface layer. The extraction method involves dissolving the surface layer (thermoplastic resin) in an appropriate solvent, separating the components in the surface layer by a known method, and fractionating the desired thermoplastic resin. Then, the thermoplastic resin and an electron donor (reference substance A) are mixed in a mass ratio of 2:1, and this is dissolved in an appropriate solvent. Then, the optical absorption spectrum is measured using a commercially available spectrophotometer (for example, U-3900 manufactured by Hitachi High-Tech Science Corporation).

[0057] On the other hand, the optical absorption spectrum is also measured when only the electron donor (reference substance A) is dissolved in the solvent. The optical absorption spectrum resulting from the transition from the HOMO level to the LUMO level of reference substance A was observed in the wavelength region below 340 nm (equivalent to 3.6 eV). Since the HOMO level of reference substance A is 5.0 eV, it can be seen that the LUMO level of reference substance A is 1.4 eV. The optical absorption spectrum is then compared with that of a system containing a thermoplastic resin. If a new absorption band appears in the wavelength range of 340 nm (equivalent to 3.6 eV) or more in the system containing a thermoplastic resin, it is determined that a charge transfer absorption band resulting from a transition to the LUMO level of the thermoplastic resin, which is located lower than 1.4 eV, has appeared. In other words, the thermoplastic resin has electron accepting properties.

[0058] Even if the charge-transfer absorption band exists, there are cases in which the charge-transfer absorption band cannot be observed sufficiently because it is buried in the intramolecular transition absorption of the electron donor (reference substance A) itself. In such a thermoplastic resin, the LUMO level is higher than 1.4 eV, and therefore, in the present invention, it is determined that the resin does not have electron accepting properties.

[0059] In addition, when a new absorption band appears in the wavelength range of 370 nm or more in combination with reference substance B (CTM-3 HOMO level 5.6 eV), it can be said that the LUMO level of the thermoplastic resin is lower than 2.3 eV. Therefore, in the present invention, a thermoplastic resin that, when combined with reference substance B, produces a new absorption band is more preferable.

[0060] As described above, examples of thermoplastic resins having electron accepting properties include polyimide resins, polyimide amide resins, polyetherimide resins, polyether ether ketone resins, polysulfone resins, polyether sulfone resins, polyether sulfide resins, polycarbonate resins, and the like. Of these, polyimide resins are preferred. In addition, it is preferable that these thermoplastic resins have an electron-withdrawing group such as a halogen atom (fluorine, chlorine, bromine, iodine), a cyano group, a nitro group, an acetyl group, a formyl group, etc., since the electron-accepting property of the thermoplastic resin is further enhanced. The surface layer may contain only one type of the above thermoplastic resin, or two or more types.

[0061] (1.3.2) Polyimide resin The thermoplastic resin is preferably a polyimide resin that is soluble in a solvent (hereinafter, also referred to as a "solvent-soluble polyimide resin"). "Soluble in a solvent" means that when 10 g of the target polyimide resin is dissolved in 100 g of an appropriate organic solvent at 25°C, the total light transmittance of the solution in the visible light region is 80% or more, and particles of 100 nm or more are not formed in the organic solvent.

[0062] The solvent-soluble polyimide resin that can be used as the thermoplastic resin may be a commercially available product, and specific examples thereof include Sixef-44 (manufactured by Hoechst Celanese), KPI-MX300F (manufactured by Kawamura Sangyo Co., Ltd.), PI-100 (manufactured by Maruzen Petrochemical Co., Ltd.), and Q-AD-X1390 (manufactured by PI Technology Research Institute Co., Ltd.).

[0063] (1.3.3) Other binder resins The surface layer may further contain a binder resin component that functions as a binder resin, in addition to the above-mentioned thermoplastic resin. However, the amount of the binder resin component is preferably 25 parts by mass or less, and more preferably 10 parts by mass or less, per 100 parts by mass of the thermoplastic resin content. The type of binder resin component is not particularly limited, and includes known thermoplastic resins that are compatible with the above-mentioned thermoplastic resins. Examples include polycarbonates, polyarylates, and the like.

[0064] (1.3.4) Charge transport material On the other hand, the charge transporting substance may be any substance having charge transporting properties, and known compounds can be used. Examples of the charge transport material include carbazole derivatives, oxazole derivatives, oxadiazole derivatives, thiazole derivatives, thiadiazole derivatives, triazole derivatives, imidazole derivatives, imidazolone derivatives, imidazolidine derivatives, bis-imidazolidine derivatives, styryl compounds, hydrazone compounds, pyrazoline compounds, oxazolone derivatives, benzimidazole derivatives, quinazoline derivatives, benzofuran derivatives, acridine derivatives, phenazine derivatives, aminostilbene derivatives, triarylamine derivatives, phenylenediamine derivatives, stilbene derivatives, benzidine derivatives, poly-N-vinylcarbazole, poly-1-vinylpyrene, and poly-9-vinylanthracene. The surface layer may contain only one type of charge transport material, or may contain two or more types. The charge transport material is preferably a triarylamine derivative or a benzidine derivative.

[0065] The amount of the charge transport material in the surface layer is preferably within a range of 10 to 500 parts by mass, and more preferably within a range of 20 to 100 parts by mass, per 100 parts by mass of the thermoplastic resin. When the amount of the charge transporting material is within the above range, the charge transporting property of the surface layer is good, and image memory and the like are unlikely to occur.

[0066] (1.3.5) Inorganic and / or organic particles The surface layer may contain inorganic particles and / or organic particles in addition to the above-mentioned thermoplastic resin and charge transport material.

[0067] Examples of inorganic particles include silica particles, tin oxide particles, aluminum oxide particles, titanium oxide particles, calcium titanate particles, and the like. Examples of organic particles include styrene-acrylic particles, melamine particles, polyfluoroethylene particles, silicone particles, and the like. Among these, silica particles, tin oxide particles, and styrene-acrylic particles are preferred. Moreover, the average primary particle size of the inorganic particles and organic particles is preferably within a range of 10 to 1000 nm from the viewpoint of adjusting the surface roughness of the surface layer. The average primary particle size is defined as the average value of 100 primary particle sizes measured directly from an electron microscope image.

[0068] The total amount of the inorganic particles and the organic particles is preferably within a range of 1 to 50% by mass, and more preferably within a range of 2 to 20% by mass, based on the total amount of the surface layer. When the total amount of the inorganic particles and the organic particles is within this range, the electron accepting property and the charge transporting property of the surface layer are unlikely to be impaired.

[0069] (1.3.6) Various additives Furthermore, the surface layer may contain various additives such as an antioxidant and silicone oil, as long as the object and effect of the present invention are not impaired. Examples of the antioxidant include the compounds described in JP-A-2000-305291.

[0070] (1.3.7) Surface layer thickness The thickness of the surface layer is appropriately selected depending on the characteristics of the thermoplastic resin and the charge transport material, and the mixing ratio thereof, but is usually preferably within the range of 1 to 30 μm, more preferably within the range of 3 to 20 μm. When the thickness of the surface layer is within this range, the photosensitive layer can be sufficiently protected by the surface layer.

[0071] (1.3.8) Volume resistivity of the surface layer The volume resistivity of the surface layer is 1×10 12 Ωcm or more is preferable, 1×10 13 More preferably, Ωcm or more, 1×10 14 More preferably, it is Ωcm or more. The volume resistivity of the surface layer is 1×10 12 When the surface resistance is Ωcm or more, the surface of the electrophotographic photosensitive member has sufficient insulating properties and good charging properties can be obtained. The volume resistivity is determined by measurement using a commercially available device (for example, Hiresta-UP (MCP-450) manufactured by Dia Instruments) in an environment of a temperature of 20° C. and a relative humidity of 50% at an applied voltage of 100 V (for 1 minute).

[0072] (1.4) Other layers As described above, the photoreceptor may include other layers between the conductive support and the photosensitive layer, if necessary, and may include, for example, the following intermediate layers.

[0073] The intermediate layer is a layer for transferring electrons generated in the charge generating layer to the conductive support side. The intermediate layer may be, for example, a layer containing conductive fine particles and a binder resin.

[0074] Examples of conductive fine particles include various metal particles; metal oxide particles such as aluminum oxide, zinc oxide, titanium oxide, tin oxide, antimony oxide, indium oxide, and bismuth oxide; tin-doped indium oxide; antimony-doped tin oxide; zirconium oxide, and the like. The intermediate layer may contain only one type of conductive fine particles, or may contain two or more types. When the intermediate layer contains two or more kinds of conductive fine particles, these may be in the form of a solid solution or may be fused together. The number average primary particle size of the conductive fine particles is preferably 0.3 μm or less, and more preferably 0.1 μm or less. The average primary particle size is defined as the average value of 100 primary particle sizes measured directly from an electron microscope image.

[0075] Examples of the binder resin include polyamide resin, casein, polyvinyl alcohol resin, nitrocellulose, ethylene-acrylic acid copolymer, vinyl chloride resin, vinyl acetate resin, polyurethane resin, gelatin, and the like. The intermediate layer may contain only one type of binder resin, or may contain two or more types of binder resin. The intermediate layer preferably contains 20 to 400 parts by mass, and more preferably 50 to 200 parts by mass, of conductive fine particles per 100 parts by mass of the binder resin. When the amount of the conductive fine particles is within this range, a layer having sufficient conductivity can be obtained.

[0076] The thickness of the intermediate layer is preferably within the range of 0.1 to 15 μm, and more preferably within the range of 0.3 to 10 μm. When the thickness of the intermediate layer is within this range, the layer can have a sufficiently high strength.

[0077] (1.5) Layer structure of electrophotographic photoreceptor The layer structure of the electrophotographic photoreceptor is not particularly limited, and may be appropriately selected depending on the performance and application required of the electrophotographic photoreceptor. For example, the conductive support / charge generating layer / charge transport layer / surface layer may be laminated in this order, or the conductive support / charge generating / transporting layer / surface layer may be laminated in this order. Alternatively, the conductive support / intermediate layer / charge generating layer / charge transport layer / surface layer may be laminated in this order, or the conductive support / intermediate layer / charge generating / transporting layer / surface layer may be laminated in this order.

[0078] (1.6) Manufacturing method of electrophotographic photoreceptor The above-mentioned electrophotographic photoreceptor can be manufactured by preparing a conductive support, carrying out a step of forming a photosensitive layer on the conductive support (photosensitive layer forming step), and a step of forming a surface layer on the photosensitive layer (surface layer forming step). Before forming the photosensitive layer, a step of forming an intermediate layer on the conductive support (intermediate layer forming step) may be carried out. The intermediate layer forming step, the photosensitive layer forming step, and the surface layer forming step will be described below, but the method for producing the electrophotographic photoreceptor of the present invention is not limited to these methods.

[0079] (1.6.1) Intermediate layer formation process In the intermediate layer forming step, the above-mentioned conductive support is prepared, and the above-mentioned intermediate layer is formed on the conductive support. The intermediate layer can be formed by applying an intermediate layer composition containing the conductive fine particles, the binder resin, and a solvent, and then solidifying the composition.

[0080] Examples of the solvent contained in the intermediate layer composition are preferably alcohols having 1 to 4 carbon atoms, such as methanol, ethanol, n-propyl alcohol, isopropyl alcohol, n-butanol, t-butanol, and sec-butanol, from the viewpoint of the coatability of the intermediate layer composition, etc. Furthermore, from the viewpoint of improving the storage stability of the intermediate layer composition and the dispersibility of the conductive fine particles, the intermediate layer composition may further contain benzyl alcohol, toluene, cyclohexanone, tetrahydrofuran, etc.

[0081] The method for preparing the intermediate layer composition is not particularly limited. For example, the solvent and the binder resin may be mixed first, and then the conductive fine particles may be added. The conductive fine particles can be dispersed by using an ultrasonic disperser, a ball mill, a sand grinder, a homomixer, or the like.

[0082] The method for applying the intermediate layer composition is not particularly limited, and may be a dip coating method, a spray coating method, a spinner coating method, a bead coating method, a blade coating method, a beam coating method, a circular amount control type application method, or the like. Furthermore, the method for drying the intermediate layer composition can be appropriately selected from known drying methods depending on the type of solvent and the thickness of the film to be formed, and heat drying is particularly preferred.

[0083] (1.6.2) Photosensitive layer formation process In the photosensitive layer forming step, a photosensitive layer is formed on the conductive support or on the intermediate layer. The method for forming the photosensitive layer is appropriately selected depending on the layer structure of the photosensitive layer. For example, when the photosensitive layer consists of only one layer of a charge generation / transport layer, a charge generation / transport layer composition containing a charge generation substance, a charge transport substance, a binder resin, a solvent, etc. is prepared, and this is applied onto the intermediate layer and solidified to form the photosensitive layer. On the other hand, when the photosensitive layer is composed of two layers, a charge generating layer and a charge transporting layer, the layers are formed in order by the following method.

[0084] (Formation of Charge Generation Layer) The method for forming the charge generation layer is not particularly limited, and the charge generation layer can be formed by applying a charge generation layer composition containing the above-mentioned charge generation material, the above-mentioned binder resin, and a solvent onto the above-mentioned conductive support (or onto the intermediate layer if an intermediate layer formation step is performed) and solidifying it.

[0085] Examples of the solvent used in the charge generating layer composition include toluene, xylene, methyl ethyl ketone, cyclohexane, ethyl acetate, butyl acetate, methanol, ethanol, propanol, butanol, methyl cellosolve, ethyl cellosolve, tetrahydrofuran, 1-dioxane, 1,3-dioxolane, pyridine, diethylamine, etc. The charge generating layer composition may contain only one of these, or may contain two or more of them.

[0086] The method for preparing the charge generating layer composition may be any method that can thoroughly mix the charge generating material, the binder resin, and the solvent. For example, the binder resin and the solvent may be mixed together, and then the charge generating material may be added. When preparing the charge generating layer composition, a dispersing device such as an ultrasonic disperser, a ball mill, a sand grinder, or a homomixer can be used.

[0087] The method for applying the charge generating layer composition is not particularly limited, and any known method can be used. Examples include dip coating, spray coating, spinner coating, bead coating, blade coating, beam coating, circular dose application, and the like. The method for solidifying the charge generating layer composition is not particularly limited, and the composition may be solidified by removing the solvent by heating or the like, or may be solidified by natural drying or the like.

[0088] (Formation of charge transport layer) The method for forming the charge transport layer is not particularly limited, and the charge transport layer can be formed by applying a charge transport layer composition containing the charge transport material, the binder resin, and a solvent, and then solidifying the composition.

[0089] Examples of the solvent include toluene, xylene, methyl ethyl ketone, cyclohexanone, ethyl acetate, butyl acetate, methanol, ethanol, propanol, butanol, tetrahydrofuran, 1,4-dioxane, 1,3-dioxolane, etc. The charge transport layer composition may contain only one of these, or may contain two or more of them.

[0090] The method for mixing the charge transport material, the binder resin, and the solvent is not particularly limited. The mixing can be carried out by using a known stirring device or the like. Furthermore, the method for applying the charge transport layer composition is not particularly limited, and any known method can be used. Examples of such methods include dip coating, spray coating, spinner coating, bead coating, blade coating, beam coating, circular amount-controlling coating, etc. The method for solidifying the charge transport layer composition is not particularly limited, and the composition may be solidified by removing the solvent by heating or the like, or may be solidified by natural drying or the like.

[0091] (1.6.3) Surface layer formation process In the surface layer forming step, a surface layer is formed on the above-mentioned photosensitive layer. The method for forming the surface layer is not particularly limited, and the surface layer can be formed, for example, by applying a surface layer composition containing the above-mentioned thermoplastic resin and solvent, and, if necessary, other components such as the above-mentioned charge transport material, onto the photosensitive layer by a known method, and then solidifying the surface layer.

[0092] Examples of the solvent contained in the surface layer composition, that is, the solvent capable of dissolving or dispersing the thermoplastic resin and the charge transport material, include toluene, xylene, methyl ethyl ketone, cyclohexanone, ethyl acetate, butyl acetate, methanol, ethanol, propanol, butanol, tetrahydrofuran, 1,4-dioxane, 1,3-dioxolane, dichloromethane, N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, etc. The surface layer composition may contain only one of these, or may contain two or more of them.

[0093] Among the above, solvents having a boiling point within the range of 40 to 150°C are preferred, and solvents having a boiling point within the range of 60 to 120°C are more preferred. When the boiling point of the solvent is 150° C. or lower, the amount of solvent remaining in the surface layer after drying is likely to be small. On the other hand, when the boiling point of the solvent is 40° C. or higher, the solvent is less likely to volatilize during storage or application of the surface layer composition, and the handleability of the surface layer composition becomes good. When two or more solvents are contained, it is preferable that the boiling points of the respective component solvents are within the above range.

[0094] The method for mixing the thermoplastic resin, the charge transport material, the solvent, etc. is not particularly limited. The mixing can be carried out by using a known stirring device or the like. The method for applying the surface layer composition is not particularly limited, and may be a known method. Examples include dip coating, spray coating, spinner coating, bead coating, blade coating, beam coating, circular dose application, and the like. Furthermore, the method for solidifying the surface layer composition is not particularly limited. For example, the surface layer composition may be solidified by removing the solvent through heating or the like, or may be solidified by natural drying or the like. The temperature when removing the solvent is preferably within the range of 50 to 140°C, more preferably within the range of 80 to 130°C. As described above, when a solvent-soluble polyimide resin is used as the thermoplastic resin, a surface layer containing a polyimide resin can be formed without heating the surface layer composition to a high temperature. Another advantage is that unreacted functional groups are less likely to remain in the surface layer.

[0095] 2. Cleaning blade (2.1) Definitions of terms related to cleaning blades (Contact force) The contact force is the cleaning blade C L When the cleaning blade C is brought into contact with the surface of the photoreceptor 10, L This is the force applied to the surface of the photoreceptor 10 as a result of applying a load to the surface.

[0096] (effective contact angle) The effective contact angle is the angle between the rubber material and the downstream edge of the image carrier in the rotation direction when the rubber material is in a bent position due to the rubber material being pressed against the image carrier. As shown in FIG. 5, L The actual angle θ1 between the tip of the tip and the surface of the photoconductor 10 is Cleaning blade C according to the present invention L is characterized in that the effective contact angle is within the range of 7 to 20°. The effective contact angle θ1 is the cleaning blade C L The deflection can be calculated using the cross-sectional shape and physical properties such as Young's modulus of the material.

[0097] (Rigid body contact angle) The rigid body contact angle is cleaning blade C L is the design value used when contacting the surface of the photoconductor. The angle θ2 shown in FIG. L Assuming that the cleaning blade C is a rigid body (shown by the dotted line), L and the tip of the photoconductor C L is the rigid body contact angle between the surface of

[0098] (Edge angle) The edge angle is the angle θ shown in Figure 5. e As shown, this is the angle of the tip edge of the rubber material, which is the contact point C with the photoconductor surface.

[0099] (free length) The free length is the length of the rubber material g The length of the protruding part from the sheet metal P g This is the portion L in FIG. 5 excluding the adhesive portion.

[0100] (wedge angle) The wedge angle is an angle between the rubber material and the ridge line on the upstream side in the rotation direction of the photoreceptor 10, as shown in FIG.

[0101] (2.2) Overview of cleaning blade The electrophotographic image forming system of the present invention has a step of removing the toner for developing the electrostatic image by pressing the edge portion of a cleaning blade against the surface of the photoconductor. The cleaning blade has an edge angle of 90° to 130° and is pressed against the surface of the photoreceptor at its tip edge, and the effective contact angle of the cleaning blade is within the range of 7° to 20°.

[0102] FIG. 5 is a conceptual diagram showing the relationship between the cleaning blade according to the present invention and an electrophotographic photosensitive member as viewed from the side. As shown in FIG. 5, the cleaning blade has an edge angle of θ e The tip edge is disposed so as to abut against the surface of the photoreceptor 10 so that the effective abutment angle θ1 falls within the above range (the portion where the tip edge abuts against the surface of the photoreceptor 10 is referred to as abutment portion C). Cleaning Blade C L The wedge angle θ3, which is the angle between the tip surface and the tangent line, is an acute angle.

[0103] The edge angle θ e When the wedge angle θ3 is 90° or more, the wedge angle θ3 becomes small, and therefore a shearing action that cleaves and spreads the layered crystals of the fatty acid metal salt is obtained in the vicinity of the blade nip portion, thereby improving the surface lubricity.

[0104] The edge angle θ e If the wedge angle θ3 is greater than 130°, the wedge angle θ3 becomes too small, and the toner particles and external additive particles present near the blade nip are pressed vertically against the photosensitive drum surface, resulting in excessive abrasiveness and insufficient lubrication. Furthermore, the force with which the trapped particles push the blade vertically upwards also increases, which may result in poor cleaning.

[0105] In one embodiment of the present invention, the edge angle θ e However, from the viewpoint of sufficiently improving the lubricity of the surface, an obtuse angle of 95° or more is preferable, and an obtuse angle of 110° or less is even more preferable.

[0106] When the effective contact angle θ1 is less than 7°, the effective contact angle θ1 is too low, so that the wedge angle θ3 becomes large and the shearing action for cleaving and spreading the layered crystals of the fatty acid metal salt cannot be obtained sufficiently. Furthermore, the peak surface pressure in the nip portion becomes smaller, which may result in poor cleaning.

[0107] The cleaning blade C according to the present invention L The effective contact angle θ1 is 7° or more, and is more preferably 9° or more from the viewpoint of the effect.

[0108] If the effective contact angle θ1 is greater than 20°, the effective contact angle θ1 is too large, so the wedge angle θ3 becomes too small, and the toner particles are not easily attracted to the cleaning blade C. L If this is the case, the force pushing the nozzles vertically upward becomes too large, which may result in poor cleaning. There is also a risk of the blade curling up.

[0109] The effective contact angle θ1 of the cleaning blade according to the present invention is 20° or less, and is more preferably 17° or less from the viewpoint of the manifestation of the effect.

[0110] (2.3) Cleaning Blade Configuration Cleaning blade C according to the present invention L It is mainly made of rubber material. The rubber material portions do not need to be all made of the same material, and may be, for example, a two-layer blade consisting of a contact layer forming the edge portion and a support layer. In the case of a two-layer structure, for example, the material of the support layer may be one having a lower permanent deformation rate than the material of the contact layer in order to suppress settling.

[0111] (Material) Cleaning blade C according to the present invention L From the viewpoints of wear resistance and moldability, the material is preferably urethane rubber.

[0112] (hardness) Cleaning blade C according to the present invention L The rubber hardness is preferably within the range of 65 to 85° in terms of hardness values ​​defined by JIS-A. If the rubber hardness is 65° or more, the blade is less likely to be pulled in, and the wedge angle θ3 does not become too small. Furthermore, if the rubber hardness is 85° or less, the surface pressure will not become too high and the abrasive force will not become too strong, and the fatty acid metal salt will not be easily removed, so that a sufficient lubricating effect can be obtained.

[0113] (Rebound elasticity) Cleaning blade C according to the present invention L The impact resilience is preferably within the range of 10 to 40°. If the resilience is within the above range, vibration is appropriately suppressed, the wedge angle θ3 is stable, and the shearing action of the fatty acid metal salt can be more effectively exerted.

[0114] (shape) Cleaning blade C according to the present invention L It is preferable that the free length L is within a range of 8.5 to 11.5 mm, and the thickness is within a range of 1.7 to 2.5 mm.

[0115] (Conditions of contact) Cleaning blade C according to the present invention L The contact force is preferably within a range of 12 to 30 (N / m) from the viewpoint of preventing incomplete wiping and curling. If the contact force is 12 (N / m) or more, there is no risk of leaving any areas unwiped, and if it is 30 (N / m) or less, there is no risk of peeling.

[0116] 3. Fatty acid metal salts The toner particles constituting the electrostatic image developing toner according to the present invention contain at least a fatty acid metal salt on the surface as an external additive.

[0117] From the viewpoint of sufficiently improving the lubricity of the surface, it is preferable that the amount of the fatty acid metal salt added is within a range of 0.20 to 0.30% by mass based on the toner base particles. When the amount of the fatty acid metal salt added is within the range of 0.20 to 0.30% by mass relative to the toner base particles, the spreading effect is sufficient, but the coverage rate of the fatty acid metal salt does not decrease, and the surface lubricity can be sufficiently improved.

[0118] From the viewpoint of improving the lubricity of the surface, it is preferable that the fatty acid metal salt is zinc stearate. Zinc stearate has a moderate negative chargeability and a moderate affinity with the electron accepting resin. In addition, the spacing between the layered crystals, determined by the alkyl chain length, becomes appropriate, and the cleavage and extensibility are good, further improving the lubricity of the surface.

[0119] If the particle size of the fatty acid metal salt is small, it can be applied more uniformly and the lubricity of the surface can be improved. From the above viewpoint, the particle size is preferably 4 μm or less, and more preferably 2 μm or less. Since the particle size of the fatty acid metal salt is small as described above, it can be applied uniformly, and the lubricity of the surface can be improved. In addition, a fatty acid metal salt having a large particle size of 10 μm or more may be used in combination with a fatty acid metal salt having a small particle size. Since fatty acid metal salts having a large particle size are easily detached from the toner base particles, the total amount of fatty acid metal salts supplied to the photoreceptor can be increased.

[0120] (Affinity between thermoplastic resin and fatty acid metal salt) The thermoplastic resin having electron accepting properties contained in the surface layer of the electrophotographic photoreceptor according to the present invention has a high affinity with the fatty acid metal salt used as a lubricant externally added to the toner for developing electrostatic images, which will be described later, and therefore the fatty acid metal salt is easily fixed to the surface of the electrophotographic photoreceptor, thereby making it possible to suppress toner filming.

[0121] 4. Toner for developing electrostatic images The electrostatic image developing toner (also simply referred to as "toner") used in the image forming system of the present invention contains toner particles having toner base particles and an external additive attached to the surface of the toner base particles. In particular, as an external additive, at least a fatty acid metal salt acting as a lubricant is contained on the surface of the toner particles. In this specification, the term "toner base particles" refers to particles that form the base of "toner particles." The "toner base particles" contain at least a binder resin, and may contain other components such as a colorant, a release agent (wax), and a charge control agent, if necessary. Particles formed by adding and adhering an external additive to the surface of a "toner base particle" are generally called "toner particles". However, when the toner base particles themselves are used as they are without adding and adhering an external additive, the toner base particles themselves may be referred to as "toner particles". The term "toner" refers to an aggregate of "toner particles."

[0122] (4.1) Toner base particles As the toner base particles according to the present invention, known toner base particles can be used. Such toner base particles are specifically composed of toner base particles containing at least a binder resin and, if necessary, a colorant. If necessary, the toner base particles may further contain other components such as a release agent and a charge control agent.

[0123] (4.2) Binder resin As the binder resin, a known resin can be used, and for example, an amorphous resin or a crystalline resin can be suitably used. In particular, it is preferable that the resin contains a styrene-acrylic resin and a crystalline polyester resin, which will be described later.

[0124] (4.2.1) Amorphous resin The amorphous resin that can be used in the present invention is not particularly limited, but known amorphous resins such as vinyl resins and polyester resins as described below, as well as urethane resins and urea resins can be preferably used.

[0125] (Vinyl resin) When a vinyl resin is used as the amorphous resin, the vinyl resin is not particularly limited as long as it is a polymer of a vinyl compound, and examples thereof include acrylate resin, styrene-acrylate resin, and ethylene-vinyl acetate resin. These may be used alone or in combination of two or more. Among the above vinyl resins, styrene-acrylic ester resins (styrene-acrylic resins) are preferred in consideration of the plasticity during thermal fixing. Therefore, although detailed explanation is omitted, it is preferable to use, as the styrene monomer, styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, α-methylstyrene, p-phenylstyrene, and p-ethylstyrene; as the (meth)acrylic acid ester monomer, acrylic acid ester monomers such as methyl acrylate, ethyl acrylate, isopropyl acrylate, n-butyl acrylate, and isobutyl acrylate; and methacrylic acid esters such as methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, isopropyl methacrylate, and isobutyl methacrylate. These styrene monomers and (meth)acrylic acid ester monomers can be used alone or in combination of two or more.

[0126] Other monomers may also be polymerized, and examples thereof include acrylic acid, methacrylic acid, maleic acid, itaconic acid, cinnamic acid, fumaric acid, maleic acid monoalkyl esters, itaconic acid monoalkyl esters, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and polyethylene glycol mono(meth)acrylate. The method for producing the styrene-acrylic resin is not particularly limited, and the resin can be produced by an emulsion polymerization method or the like.

[0127] (polyester resin) When a polyester resin is used as the amorphous resin, the amorphous polyester resin refers to a resin that does not show a clear endothermic peak in differential scanning calorimetry (DSC) among known polyester resins obtained by a polycondensation reaction between a divalent or higher carboxylic acid (polycarboxylic acid) and a divalent or higher alcohol (polyalcohol). Specifically, a clear endothermic peak means a peak whose half-width is within 15° C. when measured by differential scanning calorimetry (DSC) at a heating rate of 10° C. / min.

[0128] Examples of polycarboxylic acids include aliphatic dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,11-undecanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,13-tridecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,16-hexadecanedicarboxylic acid, and 1,18-octadecanedicarboxylic acid; aromatic dicarboxylic acids such as maleic acid, isophthalic acid, terephthalic acid, and naphthalenedicarboxylic acid; aliphatic unsaturated dicarboxylic acids such as maleic acid, fumaric acid, itaconic acid, citraconic acid, glutaconic acid, isododecenylsuccinic acid, n-dodecenylsuccinic acid, and n-octenylsuccinic acid; and divalent or higher carboxylic acids such as trimellitic acid, pyromellitic acid, naphthalenetricarboxylic acid, naphthalenetetracarboxylic acid, pyrenetricarboxylic acid, and pyrenetetracarboxylic acid.

[0129] Examples of polyhydric alcohols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-dodecanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, 1,20- Examples of the polyol include aliphatic diols such as eicosanediol; bisphenols such as bisphenol A and bisphenol F, and alkylene oxide adducts of bisphenols such as ethylene oxide adducts and propylene oxide adducts of these bisphenols; and trivalent or higher polyols such as glycerin, pentaerythritol, hexamethylol melamine, hexaethylol melamine, tetramethylol benzoguanamine, and tetraethylol benzoguanamine.

[0130] (4.2.2) Crystalline resins The toner base particles according to the present invention may contain a crystalline resin. For example, in addition to the crystalline polyesters described below, the crystalline resins described in paragraphs 0043 to 0102 of JP-A-2015-011325 can be suitably used. In particular, it is preferable from the viewpoint of production that the resin contains a hybrid crystalline polyester resin.

[0131] (Crystalline polyester resin) The crystalline polyester resin is a portion derived from a known polyester resin obtained by a polycondensation reaction between a divalent or higher carboxylic acid (polycarboxylic acid) and a divalent or higher alcohol (polyalcohol), and refers to a resin unit that has a clear endothermic peak rather than a stepwise endothermic change in differential scanning calorimetry (DSC) of the toner. Specifically, a clear endothermic peak means a peak whose half-width is within 15°C when measured at a heating rate of 10°C / min in differential scanning calorimetry (DSC) described in the Examples.

[0132] The crystalline polyester resin is not particularly limited as long as it is as defined above. For example, the crystalline polyester resin itself may be contained. Alternatively, the hybrid resin having a crystalline polyester resin unit may contain a resin having a structure in which other components are copolymerized into a main chain of a crystalline polyester resin unit, or a resin having a structure in which a crystalline polyester resin unit is copolymerized into a main chain made of other components, and a toner containing this resin may exhibit a clear endothermic peak as described above.

[0133] The crystalline polyester resin is produced from a polyvalent carboxylic acid component and a polyhydric alcohol component. In this case, the crystalline polyester resin unit is composed of the polycarboxylic acid component having the carbon number C (acid) and the polyhydric alcohol component having the carbon number C (alcohol), and the valences of the polycarboxylic acid component and the polyhydric alcohol component are each preferably 2 to 3, and particularly preferably 2.

[0134] The method for forming the crystalline polyester resin is not particularly limited, and the resin can be formed by polycondensing (esterifying) the above-mentioned polyvalent carboxylic acid and polyhydric alcohol using a known esterification catalyst.

[0135] The use ratio of the polyhydric alcohol component and the polyvalent carboxylic acid component is preferably such that the equivalent ratio [OH] / [COOH] of the hydroxy group [OH] of the diol component to the carboxy group [COOH] of the dicarboxylic acid component is 1.5 / 1 to 1 / 1.5, more preferably 1.2 / 1 to 1 / 1.2.

[0136] Examples of catalysts that can be used in producing the crystalline polyester resin include alkali metal compounds such as sodium and lithium; alkaline earth metal compounds such as magnesium and calcium; metal compounds such as aluminum, zinc, manganese, antimony, titanium, tin, zirconium, and germanium; phosphorous compounds; phosphoric acid compounds; and amine compounds.

[0137] Specific examples of the tin compound include dibutyltin oxide, tin octoate, tin dioctoate, and salts thereof. Examples of titanium compounds include titanium alkoxides such as tetra-n-butyl titanate, tetraisopropyl titanate, tetramethyl titanate, and tetrastearyl titanate; titanium acylates such as polyhydroxytitanium stearate; and titanium chelates such as titanium tetraacetylacetonate, titanium lactate, and titanium triethanolaminate. The germanium compound may include germanium dioxide. Further, examples of the aluminum compound include oxides such as polyaluminum hydroxide, aluminum alkoxides, etc., and examples of the aluminum compound include tributylaluminate, etc. These may be used alone or in combination of two or more kinds.

[0138] The polymerization temperature and polymerization time are not particularly limited, and the pressure in the reaction system may be reduced during the polymerization, if necessary.

[0139] Furthermore, in the case of a hybrid resin having a crystalline polyester resin unit, the content of the crystalline polyester resin unit is preferably within a range of 50 to 98% by mass based on the total amount of the hybrid resin. By setting the content within the above range, sufficient crystallinity can be imparted to the hybrid resin. The components and content ratio of each unit in the hybrid resin can be identified by, for example, NMR measurement or methylation reaction P-GC / MS measurement.

[0140] Here, the hybrid resin contains, in addition to the above-mentioned crystalline polyester resin unit, an amorphous resin unit other than the polyester resin, which will be described in detail below. The hybrid resin may be in any form, such as a block copolymer or a graft copolymer, so long as it contains the above-mentioned crystalline polyester resin unit and an amorphous resin unit other than the polyester resin, but is preferably a graft copolymer. By forming the graft copolymer, the orientation of the crystalline polyester resin units can be easily controlled, and sufficient crystallinity can be imparted to the hybrid resin.

[0141] From the above viewpoint, it is further preferred that the crystalline polyester resin unit is grafted to a non-crystalline resin unit other than the crystalline polyester resin as the main chain. That is, the hybrid crystalline polyester resin is preferably a graft copolymer having an amorphous resin unit other than the polyester resin as the main chain and a crystalline polyester resin unit as the side chain.

[0142] By adopting the above-mentioned embodiment, the orientation of the crystalline polyester resin units can be further enhanced, and the crystallinity of the hybrid resin can be improved.

[0143] The hybrid resin may further have a substituent such as a sulfonic acid group, a carboxy group, a urethane group, etc. The substituent may be introduced into a crystalline polyester resin unit or into an amorphous resin unit other than the polyester resin described below.

[0144] (Amorphous resin unit other than polyester resin) The non-crystalline resin unit other than the polyester resin is a portion derived from a non-crystalline resin other than the above-mentioned crystalline polyester resin. The inclusion of amorphous resin units in the hybrid resin (and further in the toner) allows the chemical structure to be characterized by selecting an appropriate analytical method from NMR measurement, P-GC / MS measurement, methylation reaction P-GC / MS measurement, etc., depending on the structure.

[0145] In addition, the amorphous resin unit is a resin unit that does not have a melting point and has a relatively high first glass transition point (Tg) when differential scanning calorimetry (DSC) is performed on a resin having the same chemical structure and molecular weight as the unit.

[0146] The amorphous resin unit is not particularly limited as long as it is as defined above. For example, with respect to a resin having a structure in which other components are copolymerized into a main chain of an amorphous resin unit, or a resin having a structure in which an amorphous resin unit is copolymerized into a main chain made of other components, if a toner containing this resin has the above-mentioned amorphous resin unit, then the resin corresponds to a hybrid resin having an amorphous resin unit.

[0147] The amorphous resin unit is preferably composed of the same type of resin as the amorphous resin contained in the binder resin (that is, a resin other than the hybrid resin). By adopting such a form, the affinity between the hybrid resin and the amorphous resin is further improved, the hybrid resin is more easily incorporated into the amorphous resin, and the charging uniformity and the like are further improved.

[0148] Here, "same type of resin" means that characteristic chemical bonds are commonly contained in the repeating units. Furthermore, the "characteristic chemical bonds" are in accordance with the "polymer classification" described in the National Institute for Materials Science (NIMS) Materials Database (http: / / polymer.nims.go.jp / PoLyInfo / guide / jp / term_polymer.html). That is, the chemical bonds that make up polymers classified into a total of 22 types, including polyacrylic, polyamide, polyanhydride, polycarbonate, polydienes, polyesters, polyhaloolefins, polyimides, polyimines, polyketones, polyolefins, polyethers, polyphenylenes, polyphosphazenes, polysiloxanes, polystyrenes, polysulfides, polysulfones, polyurethanes, polyureas, polyvinyls, and other polymers, are called "characteristic chemical bonds."

[0149] Furthermore, when the resin is a copolymer, the term "same type of resin" refers to resins that have a characteristic chemical bond in common when the chemical structures of the multiple monomer types that make up the copolymer contain monomer types having the above-mentioned chemical bonds as constituent units. Therefore, even if the properties exhibited by the resins themselves are different from each other, or the molar component ratios of the monomer species constituting the copolymer are different from each other, they are considered to be the same type of resin as long as they have characteristic chemical bonds in common.

[0150] For example, a resin (or resin unit) formed from styrene, butyl acrylate, and acrylic acid and a resin (or resin unit) formed from styrene, butyl acrylate, and methacrylic acid have at least chemical bonds that constitute polyacrylic, and therefore are the same type of resin. For further example, a resin (or resin unit) formed from styrene, butyl acrylate, and acrylic acid, and a resin (or resin unit) formed from styrene, butyl acrylate, acrylic acid, terephthalic acid, and fumaric acid have at least a chemical bond constituting polyacrylic as a common chemical bond. Therefore, they are the same type of resin.

[0151] The resin component constituting the amorphous resin unit is not particularly limited, but examples thereof include a vinyl resin unit, a urethane resin unit, and a urea resin unit. Among these, vinyl resin units are preferred because their thermoplasticity is easily controlled. The vinyl resin unit is not particularly limited as long as it is a polymer of a vinyl compound, and examples thereof include an acrylate resin unit, a styrene-acrylate resin unit, and an ethylene-vinyl acetate resin unit. These may be used alone or in combination of two or more.

[0152] The method for forming the styrene-acrylic resin unit is not particularly limited, and examples thereof include a method in which a monomer is polymerized using a known oil-soluble or water-soluble polymerization initiator. Specific examples of the oil-soluble polymerization initiator include the azo- or diazo-based polymerization initiators and peroxide-based polymerization initiators shown below.

[0153] Examples of the azo or diazo polymerization initiator include 2,2'-azobis-(2,4-dimethylvaleronitrile), 2,2'-azobisisobutyronitrile, 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis-4-methoxy-2,4-dimethylvaleronitrile, and azobisisobutyronitrile.

[0154] Examples of the peroxide polymerization initiator include benzoyl peroxide, methyl ethyl ketone peroxide, diisopropyl peroxycarbonate, cumene hydroperoxide, t-butyl hydroperoxide, di-t-butyl peroxide, dicumyl peroxide, 2,4-dichlorobenzoyl peroxide, lauroyl peroxide, 2,2-bis-(4,4-t-butylperoxycyclohexyl)propane, and tris-(t-butylperoxy)triazine.

[0155] When resin particles are formed by emulsion polymerization, a water-soluble radical polymerization initiator can be used, such as persulfates such as potassium persulfate and ammonium persulfate, azobisaminodipropane acetate, azobiscyanovaleric acid and its salts, and hydrogen peroxide.

[0156] The content of the amorphous resin unit is preferably within a range of 3 to 50% by mass based on the total amount of the hybrid resin. Furthermore, the content is more preferably within the range of 5 to 30% by mass. By setting the content within the above range, sufficient crystallinity can be imparted to the hybrid resin.

[0157] (Method of producing hybrid crystalline polyester resin (hybrid resin)) The method for producing the hybrid resin contained in the binder resin according to the present invention is not particularly limited as long as it is a method capable of forming a polymer having a structure in which the crystalline polyester resin unit and the amorphous resin unit are molecularly bonded to each other. Specific examples of the method for producing the hybrid resin include the following methods.

[0158] (1) A method for producing a hybrid resin by polymerizing an amorphous resin unit in advance and then carrying out a polymerization reaction to form a crystalline polyester resin unit in the presence of the amorphous resin unit. In this method, first, the monomers constituting the above-mentioned amorphous resin unit (preferably a vinyl monomer such as a styrene monomer and a (meth)acrylic acid ester monomer) are subjected to an addition reaction to form the amorphous resin unit. Next, in the presence of the amorphous resin unit, a polyvalent carboxylic acid and a polyhydric alcohol are polymerized to form a crystalline polyester resin unit. In this case, a hybrid resin is formed by carrying out a condensation reaction between a polyvalent carboxylic acid and a polyhydric alcohol, and also by carrying out an addition reaction between the polyvalent carboxylic acid or the polyhydric alcohol and the amorphous resin unit.

[0159] In the above method, it is preferable to incorporate a site in the crystalline polyester resin unit or the amorphous resin unit that allows these units to react with each other. Specifically, when forming the amorphous resin unit, in addition to the monomer that constitutes the amorphous resin unit, a compound having a site capable of reacting with a carboxy group [-COOH] or a hydroxy group [-OH] remaining in the crystalline polyester resin unit and a site capable of reacting with the amorphous resin unit is also used. That is, this compound reacts with a carboxy group [--COOH] or a hydroxy group [--OH] in the crystalline polyester resin unit, whereby the crystalline polyester resin unit can be chemically bonded to the amorphous resin unit. Alternatively, a compound may be used which is capable of reacting with a polyhydric alcohol or a polyvalent carboxylic acid when the crystalline polyester resin unit is formed, and which has a site capable of reacting with the amorphous resin unit. By using the above method, a hybrid resin having a structure (graft structure) in which a crystalline polyester resin unit is molecularly bonded to an amorphous resin unit can be formed.

[0160] (2) A method in which a crystalline polyester resin unit and an amorphous resin unit are formed in advance and then bonded to produce a hybrid resin. In this method, first, a polyvalent carboxylic acid and a polyhydric alcohol are subjected to a condensation reaction to form a crystalline polyester resin unit. Separately from the reaction system for forming the crystalline polyester resin unit, the monomers constituting the above-mentioned amorphous resin unit are addition-polymerized to form the amorphous resin unit. In this case, it is preferable to incorporate a site at which the crystalline polyester resin unit and the amorphous resin unit can react with each other. The method for incorporating such a reactive site is as described above, and therefore a detailed description thereof will be omitted. Next, the crystalline polyester unit formed above is reacted with an amorphous resin unit to form a hybrid resin having a structure in which the crystalline polyester resin unit and the amorphous resin unit are molecularly bonded. In addition, when the above-mentioned reactive site is not incorporated in the crystalline polyester resin unit and the amorphous resin unit, a method may be adopted in which a system in which the crystalline polyester resin unit and the amorphous resin unit coexist is formed, and a compound having a site capable of bonding to the crystalline polyester resin unit and the amorphous resin unit is added thereto. Then, a hybrid resin having a structure in which a crystalline polyester resin unit and an amorphous resin unit are molecularly bonded via the compound can be formed.

[0161] (3) A method of producing a hybrid resin by forming a crystalline polyester resin unit in advance and then carrying out a polymerization reaction to form an amorphous resin unit in the presence of the crystalline polyester resin unit. In this method, first, a polyvalent carboxylic acid and a polyhydric alcohol are polymerized by a condensation reaction to form a crystalline polyester resin unit. Next, the monomers constituting the amorphous resin unit are polymerized in the presence of the crystalline polyester resin unit to form the amorphous resin unit. In this case, similarly to the above (1), it is preferable to incorporate into the crystalline polyester resin unit or the amorphous resin unit a site that allows these units to react with each other. The method for incorporating such a reactive site is as described above, and therefore a detailed description thereof will be omitted.

[0162] By using the above method, a hybrid resin having a structure (graft structure) in which an amorphous resin unit is molecularly bonded to a crystalline polyester resin unit can be formed. Among the above formation methods (1) to (3), method (1) is preferred because it is easy to form a hybrid resin having a structure in which a crystalline polyester resin chain is grafted to an amorphous resin chain, and the production process can be simplified. In the method (1), since the amorphous resin units are formed in advance and then the crystalline polyester resin units are bonded thereto, the orientation of the crystalline polyester resin units tends to be uniform. Therefore, it is preferable because a hybrid resin suitable for the toner defined in the present invention can be reliably formed.

[0163] (4.3) Colorants As the colorant that can constitute the toner base particles, carbon black, magnetic materials, dyes, pigments, etc. can be used arbitrarily. As the carbon black, channel black, furnace black, acetylene black, thermal black, lamp black, etc. can be used. As magnetic materials, ferromagnetic metals such as iron, nickel, and cobalt, alloys containing these metals, ferromagnetic metal compounds such as ferrite and magnetite, alloys that do not contain ferromagnetic metals but exhibit ferromagnetism when heat-treated, for example, alloys known as Heusler alloys such as manganese-copper-aluminum and manganese-copper-tin, and chromium dioxide can be used.

[0164] Examples of colorants for magenta or red include CI Pigment Red 2, 3, 5, 6, 7, 15, 16, 48:1, 48:3, 53:1, 57:1, 60, 63, 64, 68, 81, 81:4, 83, 87, 88, 89, 90, 112, 114, 122, 123, 139, 144, 149, 150, 163, 166, 170, 177, 178, 184, 202, 206, 207, 209, 222, 238, and 269.

[0165] Examples of colorants for orange or yellow include CI Pigment Orange 31, CI Pigment Yellow 43, CI Pigment Yellow 12, CI Pigment Yellow 14, CI Pigment Yellow 15, CI Pigment Yellow 17, CI Pigment Yellow 74, CI Pigment Yellow 83, CI Pigment Yellow 93, CI Pigment Yellow 138, CI Pigment Orange 31, CI Pigment Orange 43, CI Pigment Yellow 12, CI Pigment Yellow 14, CI Pigment Yellow 15, CI Pigment Yellow 17, CI Pigment Yellow 74, CI Pigment Yellow 83, CI Pigment Yellow 93, CI Pigment Yellow 138, CI Pigment Orange 39, CI Pigment Orange 155, CI Pigment Orange 162, CI Pigment Yellow 180, CI Pigment Yellow 185, CI Solvent Yellow 93, and the like.

[0166] Furthermore, examples of colorants for green or cyan include CI Pigment Blue 2, 3, 15, 15:2, 15:3, 15:4, 16, 17, 60, 62, 66, CI Pigment Green 7, and the like.

[0167] These colorants can be used alone or in combination of two or more, as required. The amount of the colorant added is preferably within a range of 1 to 30% by mass, more preferably within a range of 2 to 20% by mass, based on the total amount of the toner base particles, and a mixture thereof may also be used. Within this range, color reproducibility of the image can be ensured. The colorant dispersion diameter in the toner is preferably in the range of 10 to 1000 nm, more preferably in the range of 50 to 500 nm, and even more preferably in the range of 80 to 300 nm, in terms of volume average particle diameter.

[0168] (4.4) Release agents The releasing agent constituting the toner base particles is not particularly limited, and any known releasing agent can be used. Specific examples of such waxes include polyolefin waxes such as polyethylene wax and polypropylene wax, branched chain hydrocarbon waxes such as microcrystalline wax, long chain hydrocarbon waxes such as paraffin wax and sazol wax, dialkyl ketone waxes such as distearyl ketone, carnauba wax, montan wax, ester waxes such as behenic acid behenate, trimethylolpropane tribehenate, pentaerythritol tetrabehenate, pentaerythritol diacetate dibehenate, glycerin tribehenate, 1,18-octadecanediol distearate, trimellitic acid tristearyl, and distearyl maleate, and amide waxes such as ethylenediamine behenylamide and trimellitic acid tristearylamide.

[0169] The melting point of the release agent is preferably within a range of 40 to 160°C, and more preferably within a range of 50 to 120°C. By setting the melting point within the above range, the heat-resistant storage stability of the toner is ensured, and even when fixing is performed at a low temperature, a stable toner image can be formed without causing cold offset or the like. The content of the release agent in the toner base particles is preferably within a range of 1 to 30% by mass, and more preferably within a range of 5 to 20% by mass.

[0170] (4.5) Charge control agents Furthermore, a charge control agent can be added to the toner base particles according to the present invention, if necessary. As the charge control agent, various known ones can be used.

[0171] As the charge control agent, various known compounds that can be dispersed in an aqueous medium can be used. Specific examples of the charge control agent include nigrosine dyes, metal salts of naphthenic acid or higher fatty acids, alkoxylated amines, quaternary ammonium salt compounds, azo metal complexes, metal salicylate salts or metal complexes thereof, and the like.

[0172] The content of the charge control agent is preferably within a range of 0.1 to 10% by mass, more preferably within a range of 0.5 to 5% by mass, based on the total amount of the binder resin.

[0173] (4.6) External additives The toner particles constituting the electrostatic image developing toner according to the present invention contain at least a fatty acid metal salt as an external additive. From the viewpoint of improving the charging performance, fluidity or cleaning property of the toner, known particles such as inorganic fine particles or organic fine particles, and lubricants can be added as external additives to the surface of the toner base particles. The toner particles constituting the electrostatic image developing toner used in the electrophotographic image forming system of the present invention contain at least a fatty acid metal salt as a lubricant as an external additive. The fatty acid metal salt is as described above.

[0174] Preferable examples of inorganic fine particles include inorganic fine particles made of silica, titania, alumina, strontium titanate, and the like. In particular, from the viewpoint of stress resistance, it is preferable to add large particle size silica having a number average primary particle size within the range of about 80 to 500 nm. If necessary, these inorganic fine particles may be subjected to a hydrophobic treatment.

[0175] As the organic fine particles, spherical organic fine particles having a number average primary particle size within a range of about 10 to 2000 nm can be used. Specifically, organic fine particles made of homopolymers such as styrene and methyl methacrylate, or copolymers thereof can be used.

[0176] The lubricant is used to further improve the cleaning property and transfer property, and particularly to obtain the effects of the present invention. Examples of the lubricant include metal salts of higher fatty acids such as zinc, aluminum, copper, magnesium, calcium, etc. of stearic acid, zinc, manganese, iron, copper, magnesium, etc. of oleic acid, zinc, copper, magnesium, etc. of palmitic acid, zinc, calcium, etc. of linoleic acid, zinc, calcium, etc. of ricinoleic acid, etc.

[0177] From the viewpoint of improving the lubricity of the surface, it is preferable that the fatty acid metal salt is zinc stearate. Zinc stearate has a moderate negative chargeability and a moderate affinity with the electron accepting resin. In addition, the spacing between the layered crystals, determined by the alkyl chain length, becomes appropriate, and the cleavage and extensibility are good, further improving the lubricity of the surface. These external additives may be used in combination with various other additives.

[0178] The amount of the external additive added is preferably within a range of 0.1 to 10.0% by mass relative to 100% by mass of the toner base particles.

[0179] The amount of the fatty acid metal salt added is preferably within a range of 0.20 to 0.30% by mass relative to the toner base particles in order to sufficiently improve the lubricity of the surface, and more preferably 0.2% by mass or more. When the amount of the fatty acid metal salt added is within the range of 0.20 to 0.30% by mass relative to the toner base particles, the spreading effect is sufficient, but the coverage rate of the fatty acid metal salt does not decrease, and the surface lubricity can be sufficiently improved.

[0180] Moreover, it is preferable that the average particle size of the lubricant used in the present invention is within the range of 1 to 5 μm in order to reliably prevent the occurrence of toner filming.

[0181] If the particle size of the fatty acid metal salt is small, it can be applied more uniformly and the lubricity of the surface can be improved. From the above viewpoint, the particle size is preferably 4 μm or less, and more preferably 2 μm or less.

[0182] 5. Image forming equipment The image forming apparatus used in the electrophotographic image forming system of the present invention is preferably an image forming apparatus using a general electrophotographic method, and preferably includes at least an electrophotographic photosensitive member, a charging means, an exposure means, a developing means, a transfer means, a fixing means and a cleaning means. In particular, it is preferable that the image forming apparatus used is a tandem type image forming apparatus.

[0183] FIG. 6 is an explanatory cross-sectional view showing an example of the configuration of an image forming apparatus of the present invention, and FIG. 7 is an explanatory cross-sectional view showing an example of the configuration of a main part of the image forming apparatus. As shown in FIG. 6, this image forming apparatus 100 is called a tandem type color image forming apparatus, and has four image forming units 110Y, 110M, 110C, and 110Bk, a paper feeding and conveying means 150, and a fixing means 170. An original image reading device SC is disposed on the upper portion of the main body of the image forming apparatus 100.

[0184] The image forming units 110Y, 110M, 110C, and 110Bk are arranged side by side in the vertical direction. The image forming units 110Y, 110M, 110C, and 110Bk each include a rotating drum-shaped photoconductor 111Y, 111M, 111C, and 111Bk, and, arranged in sequence along the rotation direction of the photoconductor in the outer circumferential surface area thereof, a lubricant supplying means, a charging means 113Y, 113M, 113C, and 113Bk, an exposure means 115Y, 115M, 115C, and 115Bk, a developing means 117Y, 117M, 117C, and 117Bk, a primary transfer roller (primary transfer means) 133Y, 133M, 133C, and 133Bk, a cleaning means 119Y, 119M, 119C, and 119Bk, and a lubricant removing means. A toner image of yellow (Y), magenta (M), cyan (C) and black (Bk) is formed on the photoconductors 111Y, 111M, 111C and 111Bk, respectively.

[0185] Image forming units 110Y, 110M, 110C, and 110Bk have the same configuration except that the colors of the toner images formed on photoconductors 111Y, 111M, 111C, and 111Bk are different, so the following description will be given using image forming unit 110Y as an example. Further, the electrophotographic photosensitive member, charging means, exposure means, developing means, transfer means, fixing means and cleaning means will be described in this order.

[0186] (5.1) Charging means As shown in FIG. 7, the charging unit 113Y is a unit that charges the surface of the photoconductor 111Y by a charging roller. The charging means 113Y in this example is composed of a charging roller disposed in contact with the surface of the photoconductor 111Y, and a power source that applies a voltage to the charging roller.

[0187] In the present invention, the charging means employs a proximity charging method in which a charging roller is brought into contact with or in close proximity to the surface of the photoreceptor to charge the surface.

[0188] As shown in FIG. 8, the charging roller 11 is configured such that an elastic layer 11b is laminated on the surface of a core metal 11a to reduce charging noise and provide elasticity to obtain uniform adhesion to the photoconductor 111Y, and a resistance control layer 11c is laminated on the surface of the elastic layer 11b as needed to obtain a highly uniform electrical resistance for the charging roller 11 as a whole, and a surface layer 11d is laminated on the resistance control layer 11c, and this is urged by a compression spring 11e in the direction of the photoconductor 111Y and pressed against the surface of the photoconductor 111Y with a predetermined pressing force to form a charging nip portion, and the charging roller 11 rotates in response to the rotation of the photoconductor 111Y.

[0189] The core metal 11a is made of a metal such as iron, copper, stainless steel, aluminum or nickel, or the surface of such a metal is plated to provide rust resistance and scratch resistance without impairing electrical conductivity, and its outer diameter is, for example, within the range of 3 to 20 mm.

[0190] The elastic layer 11b is made of an elastic material such as rubber to which conductive particles such as carbon black, carbon graphite, or conductive particles such as alkali metal salts or ammonium salts are added. Specific examples of elastic materials include synthetic rubbers such as natural rubber, ethylene propylene diene methylene rubber (EPDM), styrene-butadiene rubber (SBR), silicone rubber, urethane rubber, epichlorohydrin rubber, isoprene rubber (IR), butadiene rubber (BR), nitrile-butadiene rubber (NBR), and chloroprene rubber (CR), resins such as polyamide resin, polyurethane resin, silicone resin, and fluororesin, and foams such as foamed sponge, etc. The degree of elasticity can be adjusted by adding process oil, plasticizer, etc. to the elastic material.

[0191] The elastic layer 11b has a volume resistivity of 1×10 1 ~1×10 10 It is preferable that the resistivity is in the range of Ω·cm. The layer thickness is preferably within the range of 500 to 5000 μm, and more preferably within the range of 500 to 3000 μm. The volume resistivity of the elastic layer 11b is a value measured in accordance with JIS K6911.

[0192] The resistance control layer 11c is provided for the purpose of providing a uniform electrical resistance for the entire charging roller 11, but is not essential. This resistance control layer 11c can be provided by coating a material having a suitable electrical conductivity, or by covering a tube having a suitable electrical conductivity.

[0193] Specific materials constituting this resistance control layer 11c include resins such as polyamide resin, polyurethane resin, fluororesin, and silicone resin; and rubbers such as epichlorohydrin rubber, urethane rubber, chloroprene rubber, and acrylonitrile-based rubber, to which conductive agents such as conductive fine particles made of carbon black, carbon graphite, etc.; conductive metal oxide fine particles made of conductive titanium oxide, conductive zinc oxide, conductive tin oxide, etc.; and conductive fine particles made of alkali metal salts, ammonium salts, etc. have been added.

[0194] The resistance control layer 11c has a volume resistivity of 1×10 -2 ~1×10 14 It is preferably in the range of Ω·cm, and more preferably 1×10 1 ~1×10 10 It is in the range of Ω·cm. The layer thickness is preferably within the range of 0.5 to 100 μm, more preferably within the range of 1 to 50 μm, and further preferably within the range of 1 to 20 μm. The volume resistivity of the resistance control layer 11c is a value measured in accordance with JIS K6911.

[0195] The surface layer 11d is provided for the purposes of preventing the plasticizer in the elastic layer 11b from bleeding out onto the surface of the resulting charging roller, of obtaining slipperiness and smoothness on the surface of the charging roller, and of preventing the occurrence of leaks even if there are defects such as pinholes on the photoconductor 111Y, and is provided by coating the surface with a material having appropriate electrical conductivity or by covering it with a tube having appropriate electrical conductivity.

[0196] When the surface layer 11d is provided by coating a material, specific examples of the material include resins such as polyamide resin, polyurethane resin, acrylic resin, fluororesin, and silicone resin, epichlorohydrin rubber, urethane rubber, chloroprene rubber, and acrylonitrile rubber, to which a conductive agent such as conductive fine particles made of carbon black, carbon graphite, or the like; or conductive metal oxide fine particles made of conductive titanium oxide, conductive zinc oxide, conductive tin oxide, or the like has been added. Examples of the coating method include a dip coating method, a roll coating method, and a spray coating method.

[0197] In addition, in the case where the surface layer 11d is provided by covering a tube, specific examples of the tube include nylon 12, tetrafluoroethylene-perfluoroalkylvinylether copolymer resin (PFA), polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer resin (FEP), and thermoplastic elastomers such as polystyrene, polyolefin, polyvinyl chloride, polyurethane, polyester, and polyamide, to which the above-mentioned conductive agent has been added, molded into a tube shape. The tubing may be heat shrinkable or non-heat shrinkable.

[0198] The surface layer 11d has a volume resistivity of 1×10 1 ~1×10 8 It is preferably in the range of Ω·cm, and more preferably 1×10 1 ~1×10 5 Ω cm. The layer thickness is preferably within the range of 0.5 to 100 μm, more preferably within the range of 1 to 50 μm, and even more preferably within the range of 1 to 20 μm. The volume resistivity of the surface layer 11d is a value measured in accordance with JIS K6911.

[0199] Moreover, the surface layer 11d preferably has a surface roughness Rz in the range of 1 to 30 μm, more preferably in the range of 2 to 20 μm, and further preferably in the range of 5 to 10 μm.

[0200] In the charging roller 11 as described above, a charging bias voltage is applied to the core metal 11a of the charging roller 11 from the power source S1, whereby the surface of the photoconductor 111Y is charged to a predetermined potential of a predetermined polarity. Here, the charging bias voltage may be, for example, only a DC voltage, but it is preferable that it be an oscillating voltage in which an AC voltage is superimposed on a DC voltage, as this provides excellent charging uniformity. The charging bias voltage can be set within the range of, for example, about −2.5 to −1.5 kV.

[0201] As an example of the charging conditions using the charging roller shown in FIG. 8, the charging bias voltage is formed by a DC voltage of -500 V and an AC voltage that is a sine wave with a frequency of 1000 Hz and a peak-to-peak voltage of 1300 V. When this charging bias voltage is applied, the surface of the photoconductor is uniformly charged to -500 V.

[0202] (5.2) Exposure means As shown in FIG. 6, the exposure means 115Y is a means for exposing the surface of the photoconductor 111Y, which has been given a uniform potential by the charging means 113Y, based on an image signal (yellow image signal) to form an electrostatic latent image corresponding to the yellow image. The exposure means 115Y is composed of LEDs in which light emitting elements are arranged in an array in the axial direction of the photoconductor 111Y and an imaging element, or a laser optical system or the like is used.

[0203] (5.3) Developing means As shown in FIG. 6, the developing means (developing machine) 117Y is a means for supplying toner to the surface of the photoconductor 111Y, developing the electrostatic latent image formed on the surface of the photoconductor 111Y, and forming a toner image. Specifically, the developing means 117Y in this example is composed of a developing roller 118Y that has a built-in magnet and rotates while holding a developer, and a voltage application device (not shown) that applies a DC and / or AC bias voltage between the photoconductor 111Y and the developing roller 118Y. The developing means 117Y is preferably disposed at the most downstream position in the rotation direction of the photoconductor, since toner filming is likely to occur at the most downstream position.

[0204] The toner is transported to the photoconductor 111Y by the rotation of the developing roller 118Y. Then, the thin layer of toner on the developing roller 118Y comes into contact with the photoconductor 111Y to develop the electrostatic latent image on the photoconductor 111Y. The developing roller 118Y is connected to a voltage application device. A DC and / or AC bias voltage is applied to the developing roller 118Y by this voltage application device. By controlling the voltage applied to the developing roller 118Y, the developing potential (also called the developing bias) (Vdc) can be adjusted to a desired value. Due to a potential difference (development potential difference) between the potential of the electrostatic latent image carried by the developing roller 118Y and the photoconductor 111Y, an electric field is formed in a developing section where the developing roller 118Y and the photoconductor 111Y face each other.

[0205] The toner in the developer transported to the developing section by the rotation of the developing roller 118Y moves due to the force of the electric field and is attracted to the electrostatic latent image on the photoreceptor 111Y. The electrostatic latent image carried on the photoreceptor 111Y is visualized, and a toner image corresponding to the shape of the electrostatic latent image is formed on the surface of the photoreceptor 111Y.

[0206] Here, the electrostatic latent image on the photoconductor includes a non-image portion and an image portion. The non-image portion is a portion of the surface of the photoconductor 111Y that is uniformly charged by the charging roller 113Y, and the non-image portion potential (V0) is the potential of this non-image portion. The image portion is a portion of the surface of the photoconductor 111Y where the potential is reduced by exposing a part of the non-image portion to light by the exposure means, and the image portion potential (Vi) is the potential of this image portion. Moreover, the development potential (Vdc) is set to a value between the non-image portion potential (V0) and the image portion potential (Vi). In the non-image area, an electric field is formed in a direction that moves the toner from the photoconductor toward the developing means. In the image area, an electric field is formed in a direction that moves the toner from the developing means side toward the photoconductor.

[0207] In the present invention, the developing conditions of the developing machine in a normal temperature and humidity environment of 23° C. and 50% RH are set to any one of the above conditions (i) to (iii) in comparison with a low temperature and low humidity environment of 10° C. and 20% RH. (i) Decreasing the AC duty ratio (the ratio of the negative side width (time) T(-) of the AC to the period T) of the development potential applied to the development roller of the developing machine. (ii) reducing the concentration of the toner for the two-component developer in the two-component developer; (iii) Increasing the fogging margin (non-image area potential V0 of the photoconductor minus development potential Vdc)

[0208] Therefore, for example, when condition (i) is set, the voltage application device of the developing means applies a voltage so as to lower the AC duty ratio of the AC and DC superimposed on the developing roller. Moreover, when condition (iii) is set, the absolute value of Vc applied to the core of the charging roller is set high as a result. Furthermore, when the condition (ii) is set, the two-component developer used is a developer having a low toner concentration.

[0209] (5.4) Transfer means As shown in FIG. 6, a primary transfer roller 133Y constituting a transfer means is a means for transferring a toner image formed on a photoconductor 111Y onto an intermediate transfer body 131 in the form of an endless belt. The primary transfer roller 133Y is disposed in contact with the intermediate transfer body 131.

[0210] In this image forming apparatus 100, an intermediate transfer method is adopted in which toner images formed on photoconductors 111Y, 111M, 111C, and 111Bk are transferred to intermediate transfer body 131 by primary transfer rollers (primary transfer means) 133Y, 133M, 133C, and 133Bk, and each toner image transferred to intermediate transfer body 131 is transferred to transfer material P by secondary transfer roller (secondary transfer means) 217, but a direct transfer method may also be adopted in which the toner images formed on the photoconductors are transferred directly to the transfer material by transfer means.

[0211] (5.5) Cleaning means As shown in FIG. 7, the cleaning means 119Y is a means for removing the toner remaining on the surface of the photoconductor 111Y. The cleaning means 119Y in this example is composed of a cleaning blade. Details of the cleaning blade according to the present invention used as the above cleaning means are as described above, and will be described here with reference to FIGS. 6 and 7. FIG. This cleaning blade is composed of a support member and a blade member supported on this support member via an adhesive layer (not shown). The blade member is disposed so that its tip faces in the opposite direction (counter direction) to the rotation direction of the photoconductor 111Y at the contact portion with the surface of the photoconductor 111Y.

[0212] The support member is not particularly limited and may be any conventionally known member, for example, made of a rigid metal, an elastic metal, plastic, ceramic, etc. Among these, a rigid metal is preferred.

[0213] The blade member is preferably made of polyurethane. Examples of polyurethane include those obtained by reacting a polyol, a polyisocyanate, and, if necessary, a crosslinking agent. It may have a single layer structure, or may have a multi-layer structure in which a base layer and an edge layer are laminated.

[0214] As shown in FIG. 6, the intermediate transfer body 131 is wound around a plurality of rollers 137A, 137B, 137C, and 137D and is supported rotatably. A cleaning means 135 is disposed above the intermediate transfer body 131 to remove any toner remaining on the intermediate transfer body.

[0215] In this image forming apparatus 100, the photoconductor 111Y, the developing means 117Y, the cleaning means 119Y, etc. may be integrally combined and may be a process cartridge (image forming unit) configured to be detachably attached to the main body of the apparatus. Alternatively, it may be a process cartridge (image forming unit) in which the photoconductor 111Y is integrated with one or more members selected from the group consisting of the charging unit 113Y, the exposure unit 115Y, the developing unit 117Y, the primary transfer roller 133Y, and the cleaning unit 119Y.

[0216] The process cartridge 200 has a housing 201, and a photoconductor 111Y, a charging unit 113Y, a developing unit 117Y, a cleaning unit 119Y, and a primary transfer roller 133Y housed therein. Further, in the main body of the apparatus, support rails 203L and 203R are provided as means for guiding the process cartridge 200 into the main body of the apparatus. This allows the process cartridge 200 to be detachably mounted to the main body of the apparatus. These process cartridges 200 can serve as a single image forming unit that is detachably attached to the main body of the apparatus.

[0217] The paper feed conveying means 150 is provided so as to be able to convey the transfer material P in the paper feed cassette 211 to a secondary transfer roller 217 via a plurality of intermediate rollers 213 A, 213 B, 213 C, and 213 D and a registration roller 215 .

[0218] The fixing means 170 fixes the color image transferred by the secondary transfer roller 217. The paper discharge rollers 219 are provided so as to be able to place the transfer material P on a paper discharge tray 221 while nipping the transfer material P that has been subjected to the fixing process.

[0219] In the image forming apparatus 100 configured as above, toner images are formed by the image forming units 110Y, 110M, 110C, and 110Bk. Specifically, first, the surfaces of the photoconductors 111Y, 111M, 111C, and 111Bk are discharged and negatively charged by the charging means 113Y, 113M, 113C, and 113Bk. Next, the surfaces of the photoconductors 111Y, 111M, 111C, and 111Bk are exposed to light by exposure means 115Y, 115M, 115C, and 115Bk based on image signals, forming electrostatic latent images. Next, developing means 117Y, 117M, 117C, and 117Bk apply toner to the surfaces of the photoconductors 111Y, 111M, 111C, and 111Bk to develop them, thereby forming toner images.

[0220] Next, primary transfer rollers (primary transfer means) 133Y, 133M, 133C, and 133Bk are brought into contact with the intermediate transfer body 131 which is rotating. Thereby, the toner images of each color formed on the photoconductors 111Y, 111M, 111C, and 111Bk are successively transferred onto the rotating intermediate transfer body 131, thereby transferring a color image (primary transfer). During the image forming process, the primary transfer roller 133Bk is constantly in contact with the photoconductor 111Bk. On the other hand, the other primary transfer rollers 133Y, 133M, and 133C come into contact with the corresponding photoconductors 111Y, 111M, and 111C, respectively, only during color image formation.

[0221] Then, after the primary transfer rollers 133Y, 133M, 133C, and 133Bk are separated from the intermediate transfer body 131, the toner remaining on the surfaces of the photoconductors 111Y, 111M, 111C, and 111Bk is removed by cleaning means 119Y, 119M, 119C, and 119Bk. Next, the surfaces of the photoconductors 111Y, 111M, 111C, and 111Bk are neutralized by neutralizing means (not shown) as necessary, and then negatively charged by charging means 113Y, 113M, 113C, and 113Bk.

[0222] Meanwhile, a transfer material P (e.g., a support carrying the final image, such as plain paper or a transparent sheet) contained in a paper feed cassette 211 is fed by a paper feed conveying means 150 and conveyed via multiple intermediate rollers 213A, 213B, 213C, 213D and a resist roller 215 to a secondary transfer roller (secondary transfer means) 217. Then, the secondary transfer roller 217 is brought into contact with the rotating intermediate transfer body 131, and the color images are transferred onto the transfer material P all at once (secondary transfer). The secondary transfer roller 217 comes into contact with the intermediate transfer body 131 only when performing secondary transfer onto the transfer material P. Thereafter, the transfer material P onto which the color image has been collectively transferred is separated at a portion of the intermediate transfer body 131 where the curvature is large.

[0223] The transfer material P onto which the color images have been transferred all at once in this manner is fixed by fixing means 170, and then is sandwiched by paper discharge rollers 219 and placed on a paper discharge tray 221 outside the apparatus. After the transfer material P onto which the color image has been collectively transferred is separated from the intermediate transfer body 131, the remaining toner on the intermediate transfer body 131 is removed by cleaning means 135. EXAMPLES

[0224] Specific examples of the present invention will be described below together with comparative examples, but the present invention is not limited thereto. In the examples, "parts" and "%" mean "parts by mass" and "% by mass" unless otherwise specified.

[0225] [Preparation of electrophotographic photoreceptor and confirmation of electron acceptance] [Preparation of Electrophotographic Photoreceptor 1] An electrophotographic photoreceptor 1 was prepared as follows.

[0226] <Preparation of conductive support> The surface of a cylindrical aluminum support having a diameter of 30 mm was machined to prepare a conductive support having a surface roughness Rz of 1.5 (μm).

[0227] <Formation of the intermediate layer> The following components were dispersed batchwise for 10 hours using a sand mill to obtain a dispersion.

[0228] (composition) Binder resin: Polyamide resin CM8000 (manufactured by Toray Industries, Inc.) 1 part by weight Conductive particles: Titanium oxide SMT500SAS (manufactured by Teika Co., Ltd.) 3 parts by weight Methanol 10 parts by weight

[0229] Thereafter, the above dispersion was diluted two-fold with methanol and allowed to stand overnight. After being left to stand, the dispersion was filtered (filter: Rigimesh 5 μm filter manufactured by Nippon Pall Corporation was used) to obtain an intermediate layer composition. The intermediate layer composition was applied onto the conductive support by a dip coating method, and then solidified. The dry thickness of the intermediate layer was 2 μm.

[0230] <Formation of photosensitive layer> As the photosensitive layer, the following charge generating layer and charge transport layer were formed.

[0231] (1) Formation of the charge generating layer The following components were mixed and dispersed for 10 hours using a sand mill to prepare a charge generating layer composition.

[0232] (composition) Charge generating material: titanyl phthalocyanine pigment (a titanyl phthalocyanine pigment having a maximum diffraction peak at at least 27.3° in a Cu-Kα characteristic X-ray diffraction spectrum measurement) 20 parts by mass Binder resin: Polyvinyl butyral resin (#6000-C: manufactured by Denki Kagaku Kogyo Co., Ltd.) 10 parts by mass t-Butyl acetate 700 parts by mass 4-Methoxy-4-methyl-2-pentanone 300 parts by mass

[0233] The charge generating layer composition was applied onto the intermediate layer by dip coating and then solidified. The dry thickness of the charge generating layer (also referred to as the "dry film thickness") was 0.3 μm.

[0234] (2) Formation of the charge transport layer The following components were mixed to prepare a charge transport layer composition.

[0235] (composition) Charge transport material (CTM-1 having the structure represented by the following chemical formula) 150 parts by mass Binder resin: Polycarbonate (Z-300, manufactured by Mitsubishi Gas Chemical Co., Ltd.) 300 parts by mass Antioxidant: Irganox 1010 (BASF Japan) 6 parts by weight Tetrahydrofuran 1600 parts by mass Toluene 400 parts by mass Silicone oil: KF-54 (Shin-Etsu Chemical Co., Ltd.) 1 part by weight

[0236] [ka]

[0237] The charge transport layer composition was applied onto the charge generating layer by dip coating and allowed to solidify. The dry thickness of the charge transport layer was 25 μm.

[0238] <Formation of surface layer> The following components were mixed to prepare a surface layer composition.

[0239] (composition) Charge transport material (compound CTM-1 represented by the above chemical formula) 150 parts by weight Thermoplastic resin: 300 parts by mass of fluorine-containing solvent-soluble polyimide resin A1 (Sixef-44, manufactured by Hoechst Celanese) Antioxidant: Irganox 1010 (BASF Japan) 6 parts by weight Tetrahydrofuran (boiling point 66°C) 2000 parts by mass Silicone oil: KF-54 (Shin-Etsu Chemical Co., Ltd.) 1 part by weight

[0240] The surface layer composition was applied onto the charge generating layer by dip coating and then solidified. The dry thickness of the surface layer was 10 μm. The surface layer A1 was formed by the above procedure.

[0241] [Confirmation of electron-accepting ability] <Observation of optical absorption spectrum using reference material A> A thermoplastic resin and an electron donor (reference substance A) with a known HOMO level were mixed in a mass ratio of 2:1, and the mixture was dissolved in tetrahydrofuran, and the optical absorption spectrum was measured with a spectrophotometer. On the other hand, the optical absorption spectrum of the electron donor (standard substance A) dissolved in the solvent alone was measured by a spectrophotometer. When the optical absorption spectra of these materials were compared, an absorption band with an absorption edge of 620 nm was observed in the mixture containing the thermoplastic resin. Therefore, since a new absorption band was observed in the wavelength region of 340 nm or more, it was determined that the above thermoplastic resin has electron accepting properties.

[0242] <Observation of optical absorption spectrum using reference material B> In the observation of the optical absorption spectrum using the above-mentioned reference material A, the optical absorption spectrum was measured in the same manner except that reference material A was replaced with reference material B. When the optical absorption spectra were compared, an absorption band with an absorption edge of 480 nm or more was observed in the mixture containing the thermoplastic resin. Therefore, since a new absorption band was observed in the wavelength region of 370 nm or more, it was determined that the above thermoplastic resin has electron accepting properties. By the above procedure, an electrophotographic photoreceptor 1 was produced.

[0243] [Preparation of Electrophotographic Photoreceptor 2] An electrophotographic photoreceptor 2 was produced in the same manner as the electrophotographic photoreceptor 1, except that in the preparation of the surface layer composition in <Formation of Surface Layer>, the thermoplastic resin was changed to a polyimide resin A2 (KPI-MX300F, manufactured by Kawamura Sangyo Co., Ltd.) to form the surface layer A2.

[0244] [Confirmation of electron-accepting ability] In addition, the presence or absence of electron-accepting properties was determined by observing the optical absorption spectra using reference substances A and B in the same manner, and it was determined that the thermoplastic resin had electron-accepting properties in both cases.

[0245] [Preparation of Electrophotographic Photoreceptor 3] An electrophotographic photoreceptor 3 was produced in the same manner as the electrophotographic photoreceptor 1, except that in the preparation of the surface layer composition in <Formation of Surface Layer>, the thermoplastic resin was changed to polyethersulfone B (Sumikaexcel PES, manufactured by Sumitomo Chemical Co., Ltd.) to form the surface layer B.

[0246] [Confirmation of electron-accepting ability] In addition, the presence or absence of electron-accepting properties was determined by observing the optical absorption spectra using reference substances A and B in the same manner, and it was determined that the thermoplastic resin had electron-accepting properties in both cases.

[0247] [Preparation of Electrophotographic Photoreceptor 4] An electrophotographic photoreceptor 4 was produced in the same manner as the electrophotographic photoreceptor 1, except that in the preparation of the surface layer composition in <Formation of Surface Layer>, the thermoplastic resin was changed to polyimide resin A3 (PI-100, manufactured by Maruzen Petrochemical Co., Ltd.) to form the surface layer A3.

[0248] [Confirmation of electron-accepting ability] In addition, the presence or absence of electron-accepting properties was determined by observing the optical absorption spectra using reference substances A and B in the same manner. When reference substance A was used, it was determined that the thermoplastic resin had electron-accepting properties, but when reference substance B was used, the thermoplastic resin did not have electron-accepting properties.

[0249] [Preparation of Electrophotographic Photoreceptor 5] An electrophotographic photoreceptor 5 was produced in the same manner as the electrophotographic photoreceptor 1, except that in the preparation of the surface layer composition in <Formation of Surface Layer>, the thermoplastic resin was changed to polyarylate resin C (M-2000H manufactured by Unitika Ltd.) to form the surface layer C.

[0250] [Confirmation of electron-accepting ability] In addition, when the presence or absence of electron accepting property was determined by observing the excitation spectrum using reference materials A and B in the same manner, it was found that the thermoplastic resin did not have electron accepting property in any case where reference material A and B were used.

[0251] [Cleaning blade manufacturing] [Preparation of cleaning blade A] <Production of rubber sheets> Using 4,4'-diphenylmethane diisocyanate, polyester polyol, and short-chain polyol as raw materials, a urethane rubber sheet having a thickness of 2 mm was produced by a known centrifugal molding method. While changing the compounding ratio, a rubber sheet of rubber material A with hardness of 72° and impact resilience of 11° was produced. The above rubber hardness is a hardness value defined by JIS-A.

[0252] <Edge formation> Rubber sheet A was cut with a blade at an angle of 10° to the vertical direction to form an edge portion with an edge angle of 100°.

[0253] <Cutting and gluing cleaning blades> Further, the blade was cut vertically to a size of 340 mm x 14.0 mm. The blade was heat-bonded to a metal plate with a bonding margin of 4 mm using a thermosetting adhesive to produce cleaning blade A with a free length of 10.0 mm.

[0254] [Preparation of cleaning blade B] In <Formation of Edge Part>, a cleaning blade was produced in the same manner as cleaning blade A, except that the edge angle was changed to 105°.

[0255] [Preparation of cleaning blade C] In <Preparation of Rubber Material Rubber Sheet>, the same procedure was followed as for cleaning blade A, except that a rubber sheet of rubber material B having a hardness of 77° and a rebound resilience of 15° was prepared.

[0256] [Preparation of cleaning blade D] In <Formation of Edge Part>, a cleaning blade was produced in the same manner as cleaning blade A, except that the edge angle was changed to 110°.

[0257] [Preparation of cleaning blade E] In <Formation of Edge Part>, a cleaning blade was produced in the same manner as cleaning blade A, except that the edge angle was changed to 116°.

[0258] [Preparation of cleaning blade F] In <Formation of Edge Part>, a cleaning blade was produced in the same manner as cleaning blade A, except that the edge angle was changed to 90°.

[0259] [Preparation of cleaning blade G] In <Formation of Edge Part>, a cleaning blade was produced in the same manner as cleaning blade A, except that the edge angle was changed to 95°.

[0260] [Preparation of cleaning blade H] In <Formation of Edge Part>, a cleaning blade was produced in the same manner as cleaning blade A, except that the edge angle was changed to 85°.

[0261] [Preparation of cleaning blade I] In <Formation of Edge Part>, a cleaning blade was produced in the same manner as cleaning blade A, except that the edge angle was changed to 135°.

[0262] [Toner manufacturing] <Synthesis of hybrid crystalline polyester resin (c1)> The raw material monomers for the following addition polymerization resin (styrene-acrylic resin: StAc) unit, including a bireactive monomer, and a radical polymerization initiator were placed in a dropping funnel. Styrene 34 parts by weight n-Butyl acrylate 12 parts by weight Acrylic acid 2 parts by mass Polymerization initiator: di-t-butyl peroxide 7 parts by mass

[0263] Furthermore, the raw material monomers of the polycondensation resin (crystalline polyester resin: CPEs) unit described below were placed in a four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer and a thermocouple, and were heated to 170° C. to dissolve. Sebacic acid 369 parts by mass 1,10-Decanediol 318 parts by mass

[0264] Next, the raw material monomer of the addition polymerization resin (StAc) was added dropwise over 90 minutes while stirring, and after maturing for 60 minutes, the unreacted addition polymerization monomer was removed under reduced pressure (8 kPa). The amount of the monomer removed at this time was extremely small compared to the raw material monomer ratio of the resin. Thereafter, 0.8 parts by mass of Ti(OBu)4 was added as an esterification catalyst, the temperature was raised to 235°C, and the reaction was carried out at normal pressure (101.3 kPa) for 5 hours and further at reduced pressure (8 kPa) for 1 hour.

[0265] Next, after cooling to 200° C., the mixture was reacted under reduced pressure (20 kPa) for 1 hour to obtain a hybrid crystalline polyester resin (c1). The hybrid crystalline polyester resin (c1) contained 8 mass % of resin (StAc) units other than CPEs (crystalline polyester resin) based on the total amount of the hybrid crystalline polyester resin (c1), and was a resin in which CPEs were grafted to StAc. The hybrid crystalline polyester resin (c1) had a number average molecular weight (Mn) of 9000 and a melting point (Tc) of 76°C.

[0266] <Preparation of Aqueous Dispersion of Hybrid Crystalline Polyester Resin Particles (C1)> 30 parts by mass of the above crystalline polyester resin was melted and transferred in the molten state to an emulsifying and dispersing machine "Cavitron CD1010" (manufactured by Eurotech Co., Ltd.) at a transfer rate of 100 parts by mass per minute. Simultaneously with the transfer of the molten crystalline polyester resin, dilute ammonia water with a concentration of 0.37% by mass, which was prepared by diluting 70 parts by mass of reagent ammonia water with ion-exchanged water in an aqueous solvent tank, was transferred to the emulsifying and dispersing machine "Cavitron CD1010" (manufactured by Eurotech Co., Ltd.) at a transfer rate of 0.1 liters per minute while being heated to 100°C by a heat exchanger. The emulsifier / disperser "Cavitron CD1010" (Eurotech Co., Ltd.) was operated at a rotor speed of 60Hz and a pressure of 5kg / cm. 2 By operating under the above conditions, a fine particle dispersion of a crystalline polyester resin having a solid content of 30 parts by mass was prepared. At this time, the particles contained in the above-mentioned crystalline polyester resin fine particle dispersion had a volume-based median diameter of 200 nm.

[0267] <Preparation of Aqueous Dispersion of Amorphous Resin Particles (X1)> (First stage polymerization) A 5 L reaction vessel equipped with a stirrer, a temperature sensor, a cooling tube, and a nitrogen introducing device was charged with 8 parts by mass of sodium dodecyl sulfate and 3,000 parts by mass of ion-exchanged water, and the internal temperature was raised to 80° C. while stirring at a stirring speed of 230 rpm under a nitrogen stream. After the temperature was raised, a solution of 10 parts by mass of potassium persulfate in 200 parts by mass of ion-exchanged water was added, and the liquid temperature was again raised to 80° C. Styrene 480 parts by weight n-Butyl acrylate 250 parts by weight Methacrylic acid 68.0 parts by mass The monomer mixture consisting of the above was added dropwise over 1 hour, and then the mixture was heated and stirred at 80° C. for 2 hours to carry out polymerization, thereby preparing a dispersion liquid (x1) of resin fine particles.

[0268] (Second stage polymerization) A 5 L reaction vessel equipped with a stirrer, a temperature sensor, a cooling tube, and a nitrogen introducing device was charged with a solution of 7 parts by mass of sodium polyoxyethylene (2) dodecyl ether sulfate dissolved in 3,000 parts by mass of ion-exchanged water, heated to 98°C, and then charged with 260 parts by mass of a dispersion liquid (x1) of resin fine particles, Styrene (St) 284 parts by mass n-Butyl acrylate (BA) 92 parts by weight Methacrylic acid (MAA) 13 parts by weight n-Octyl-3-mercaptopropionate 1.5 parts by mass Release agent: behenic acid behenate (melting point 73°C) 190 parts by weight A solution of the monomer and release agent dissolved at 90°C was added, and the mixture was mixed and dispersed for 1 hour using a mechanical disperser "CLEARMIX" (manufactured by M Technique Co., Ltd.) with a circulation path to prepare a dispersion containing emulsified particles (oil droplets). Next, an initiator solution in which 6 parts by mass of potassium persulfate was dissolved in 200 parts by mass of ion-exchanged water was added to this dispersion, and the system was heated and stirred at 84°C for 1 hour to carry out polymerization, thereby preparing a dispersion of resin microparticles (x2).

[0269] (Third stage polymerization) Further, 400 parts by mass of ion-exchanged water was added to the dispersion liquid (x2) of the resin fine particles and mixed thoroughly, and then a solution in which 11 parts by mass of potassium persulfate was dissolved in 400 parts by mass of ion-exchanged water was added, and the mixture was stirred at a temperature of 82° C. Styrene (St) 350 parts by mass n-Butyl acrylate (BA) 215 parts by mass Acrylic acid (AA) 30 parts by weight n-Octyl-3-mercaptopropionate 8 parts by mass After the dropwise addition, polymerization was carried out by heating and stirring for 2 hours, and then the mixture was cooled to 28°C to prepare an aqueous dispersion (X1) of amorphous resin particles made of vinyl resin. The resulting aqueous dispersion (X1) of amorphous resin fine particles had a volume-based median diameter of 220 nm, a glass transition temperature (Tg) of 55° C., and a weight average molecular weight (Mw) of 32,000.

[0270] <Preparation of Water-Based Dispersion of Colorant Particles (Cy1)> 90 parts by mass of sodium dodecyl sulfate was added to 1600 parts by mass of ion-exchanged water. While stirring this solution, 420 parts by mass of copper phthalocyanine (CI Pigment Blue 15:3) was gradually added. Then, the solution was dispersed using a stirring device "Clearmix" (manufactured by M Technique Co., Ltd.) to prepare an aqueous dispersion of colorant particles (Cy1). With respect to the resulting aqueous dispersion (Cy1) of colorant particles, the volume-based median diameter of the colorant particles was 110 nm.

[0271] <Production of Cyan Toner 1> A reaction vessel equipped with a stirrer, a temperature sensor, and a cooling tube was charged with 288 parts by mass (solid content equivalent) of the aqueous dispersion of amorphous resin microparticles (X1), 70 parts by mass (solid content equivalent) of the aqueous dispersion of hybrid crystalline polyester resin microparticles (C1), and 2,000 parts by mass of ion-exchanged water, and then a 5 mol / L aqueous sodium hydroxide solution was added to adjust the pH to 10. Then, 30 parts by mass (solid content equivalent) of an aqueous dispersion of colorant particles (Cy1) was added, and then an aqueous solution in which 60 parts by mass of magnesium chloride was dissolved in 60 parts by mass of ion-exchanged water was added over 10 minutes at 30° C. with stirring. After that, the system was left to stand for 3 minutes, and then heating was started. The system was heated to 80° C. over 60 minutes, and the particle growth reaction was continued while maintaining the temperature at 80° C. In this state, the particle size of the associated particles was measured using a Coulter Multisizer 3 (manufactured by Coulter Beckman), and when the volume-based median diameter reached 6.0 μm, an aqueous solution of 190 parts by mass of sodium chloride dissolved in 760 parts by mass of ion-exchanged water was added to stop particle growth. The temperature was then increased and the particles were heated and stirred at 90°C to promote particle fusion. When the average circularity of the toner reached 0.945 (HPF detection number: 4,000 particles) using an "FPIA-2100" toner average circularity measuring device (Sysmex Corporation), the particles were cooled to 30°C at a cooling rate of 2.5°C / min. Next, the toner cake was subjected to solid-liquid separation, and the dehydrated toner cake was redispersed in ion-exchanged water and subjected to solid-liquid separation. This operation was repeated three times for washing, and then the toner cake was dried at 40° C. for 24 hours to obtain toner base particles 1.

[0272] To 100 parts by mass of the obtained toner base particles 1, 0.6 parts by mass of hydrophobic silica (number average primary particle size=12 nm, hydrophobicity=68), 1.0 part by mass of hydrophobic titanium oxide (number average primary particle size=20 nm, hydrophobicity=63), and 0.30 parts by mass of zinc stearate as a fatty acid metal salt were added, and the mixture was mixed in a "Henschel Mixer" (manufactured by Mitsui Miike Chemical Engineering Co., Ltd.) at a rotor peripheral speed of 35 mm / sec at 32°C for 20 minutes. After that, an external additive treatment was performed to remove coarse particles using a sieve with 45 μm openings, thereby obtaining cyan toner 1 with a volume average particle size of 6.1 μm.

[0273] <Production of Cyan Toner 2> Cyan toner 2 was obtained in the same manner as in the production of cyan toner 1, except that 0.30 parts by mass of calcium stearate was added as the fatty acid metal salt.

[0274] <Production of Cyan Toner 3> Cyan toner 3 was obtained in the same manner as in the production of cyan toner 1, except that 0.15 parts by mass of zinc stearate was added as the fatty acid metal salt.

[0275] <Production of Cyan Toner 4> Cyan toner 4 was obtained in the same manner as in the production of cyan toner 1, except that 0.20 parts by mass of zinc stearate was added as the fatty acid metal salt.

[0276] [Manufacturing of developer] A ferrite carrier having a volume average particle size of 60 μm coated with an acrylic resin was added to and mixed with each of the cyan toners 1 to 4 so that the toner concentration in the developer was 6.5% by mass, thereby producing each of the developers.

[0277] [Examples 1 to 17 and Comparative Examples 1 to 3] In a bizhub C650i machine (manufactured by Konica Minolta), the drum unit was disassembled, and the prepared photoconductors 1 to 5 and cleaning blades A to I were replaced, respectively, and an image forming system was prepared using developers containing toners 1 to 4 in which the amount of fatty acid metal salt added and the material were changed as shown in Table I, and the image forming system was installed in the cyan color position of the machine. An image chart having a cyan solid band patch 15 mm wide in the conveying direction and 290 mm wide in the direction perpendicular to the conveying direction was printed on 200,000 sheets of A4 paper on both sides. A 1 cm square partition area was set on the photoconductor as shown in FIG. 9, and the number of occurrences of toner filming within the area was counted.

[0278] [Table 1]

[0279] [evaluation] The number of toner filmings was counted in 10 square sections along the longitudinal direction of the photoreceptor, and the total number of toner filmings in the 10 sections was counted. The fewer the total number of toner filmings, the better, and a total number of toner filmings of 40 or less was considered to be acceptable.

[0280] (summary) As shown in Table I above, the examples using an electrophotographic photoreceptor containing in its surface layer a resin that is deemed to have electron accepting properties and using a cleaning blade with an edge angle in the range of 90 to 130° and an effective abutment angle in the range of 7 to 20° are superior overall to the comparative examples that do not use such a resin, as can be seen from the total number of filming occurrences. Furthermore, it can be seen that it is more preferable that the electron accepting property is judged to be present both when reference substance A is used and when reference substance B is used.

[0281] As can be seen from a comparison of Examples 1 to 4, even if the type of resin in the surface layer of the electrophotographic photosensitive member, the edge angle of the cleaning blade, the rigid body contact angle, and the hardness and rebound resilience of the rubber material are changed within the range of the present invention, the total number of filming occurrences can be suppressed to the same level.

[0282] From Examples 1 and 5, it can be seen that the effect of the present invention is not limited to a specific type of fatty acid metal salt material.

[0283] As can be seen from the comparison of Examples 1, 6 and 7, when the fatty acid metal salt used as the external additive of the toner is zinc stearate, the total number of filmings that occurs can be reduced when the amount of added is within the range of 0.20 to 0.30 parts by mass.

[0284] Although not shown in the table, when the effective contact angle was 6°, toner slipped through, causing poor image quality, and therefore the evaluation was discontinued. Furthermore, when the effective contact angle was 21°, blade curl occurred, and therefore the evaluation was discontinued. As can be seen from the comparison between Example 1 and Examples 8 to 11, when the effective contact angle of the cleaning blade is within the range of 7 to 20°, the total number of filmings that occurs can be suppressed.

[0285] As can be seen from a comparison of Examples 1, 3, 12, 13, 16, and 17 with Comparative Examples 2 and 3, when the edge angle of the cleaning blade is within the range of 90 to 130°, the total number of filmings can be reduced.

[0286] As can be seen from the comparison with Examples 1, 2 and 14, when polyimide is used as the resin for the surface layer, the total number of occurrences of filming can be reduced.

[0287] As can be seen from the comparison between Example 1, Example 15, and Comparative Example 1, the total number of filmings occurring can be reduced when the surface layer has electron accepting properties, and further, the total number of filmings occurring can be reduced even more when both reference substances A and B have electron accepting properties. [Explanation of symbols]

[0288] 11 Charging roller 11a Core metal 11b Elastic layer 11c Resistance Control Layer 11d surface layer 11e Compression spring 100 Image forming device 110Y, 110M, 110C, 110Bk Image forming unit 10, 111Y, 111M, 111C, 111Bk photoconductor 113Y, 113M, 113C, 113Bk Charging means, charging roller 115Y, 115M, 115C, 115Bk Exposure means 117Y, 117M, 117C, 117Bk developing means 118Y, 118M, 118C, 118Bk developing roller 119Y, 119M, 119C, 119Bk, 135 Cleaning means 131 Intermediate transfer body 133Y, 133M, 133C, 133Bk Primary transfer roller (transfer means) 137A, 137B, 137C, 137D Rollers 150 Paper feed conveying means 170 Fixing means 200 Process Cartridge 201 Case 203R, 203L Support Rail 211 Paper feed cassette 213A, 213B, 213C, 213D Intermediate roller 215 Resist Roller 217 Secondary transfer roller (transfer means) 219 Paper ejection roller 221 Paper output tray S1 power supply P Transfer material SC Original Image Scanner C L Cleaning blade P g sheet metal C Contact part E Edge part T Toner particles M fatty acid metal salt F Force acting on toner particles from cleaning blade F N The force that presses toner particles or hard particles vertically against the surface of the photoconductor θ1 effective contact angle θ2 rigid body contact angle θ3 wedge angle θ e Edge Angle L free length d Thickness

Claims

[Claim 1] forming an electrostatic latent image on at least a photoconductor; developing the image with a toner for developing an electrostatic image; and removing the toner for developing the electrostatic image by pressing a ridge portion of a cleaning blade against the surface of the photoconductor, the photoreceptor has a photosensitive layer and a surface layer on a conductive support, the surface layer containing at least a thermoplastic resin having a LUMO level lower than 1.4 eV; The toner particles constituting the electrostatic image developing toner contain at least a fatty acid metal salt on the surface as an external additive, a cleaning blade having an edge angle in the range of 90 to 130° and a tip edge portion of the cleaning blade being pressed against the surface of the photoreceptor, and an effective contact angle of the cleaning blade being in the range of 7 to 20°.

Citation Information

Patent Citations

  • Image forming apparatus

    JP2005091500A

  • Electrophotographic photoreceptor

    JP2006018153A

  • Toner, developer, and image forming apparatus

    JP2014178496A

  • Electrophotographic image forming apparatus

    JP2017058567A

  • Cleaning device and image formation device

    JP2017107030A